Fermented residue derived biochar for reverse water gas shift reaction: boosting CO selectivity and enabling direct use of unpurified biohydrogen for synthetic fuel production - Muhammad Adnan Sami Khan; Fuke Ai; Quanguo Zhang; Wang Xin; Haiyan Xu; Haitao Wu; Zhiping Zhang (Fuel, 2027)

Prediction of the sustainable concrete strength using machine Learning-based boosting and expression techniques - Muhammad Waqas Ashraf; Adnan Khan; Yongming Tu; Tongfang Wang; Chao Wang (European Journal of Environmental and Civil Engineering, 2026)

CRISPR–cas systems in pharmacology: functional pharmacogenomics, drug screening, resistance, and therapeutic translation - Muhammad Saeed Akhtar; Adnan Amin (Functional & Integrative Genomics, 2026)

LQI-based adaptive super-twisting sliding mode controller for a pressurized water reactor in load-following operation - Hailemichael Guadie Mengsitu; Xiuchun Luan; Hetao Sun; Fabiano Gibson Daud Thulu; Muhammad Adnan (Annals of Nuclear Energy, 2026)

Numerical investigation of PCM-based thermal energy storage device of nuclear power plants containment using a fins configuration - Muhammad Adnan; Hui Wang; Yanlu Wang; Cao Xiaxin; Hailemichael Guadie Mengsitu; Arif Aziz; Jamil Khan (Annals of Nuclear Energy, 2026)

Diversifying tropical agroforestry: High-value understory crops in rubber and coconut systems - Muhammad Zeeshan Ul Haq; Yaqi Zhao; Muhammad Adnan Ul Haq; Hafiza Amina Iqbal; Waqar Ahmed; Jianfeng Yang; Zhigang Li; Chao Zu; Jie Kang; Weiquan Zheng; Gangqiang Dong; Can Wang (Agricultural Systems, 2026)

AM fungal and rhizobacteria jointly enhance vegetable waste decomposition in soils and harvest environmental and agronomic benefits in dryland - Muhammad Maqsood Ur Rehman; Sidra Khattak; Ling Zhao; Yun-Li Xiao; Ying Zhu; Awais Iqbal; Rafi Ullah; Nang Chang; Muhammad Abrar; Jian-Ming Li; Hao Sun; Adnan Khan; et al. (Agriculture, Ecosystems & Environment, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Interfacial construction of Co-MOF/NiCu-MOF for enhanced visible-light-driven peroxymonosulfate activation and ciprofloxacin degradation: Mechanistic insights, kinetics and stability study - Raza Ullah; Nasim Ullah; Abdul Qadir; Muzamil Ahmad; Alamgir; Muhammad Fayaz; Muhammad Rafiq; Adeel Ahmed; Muhammad Adnan; Fangqing Wang; Bing Yu; Hailin Cong (Journal of Environmental Chemical Engineering, 2026)

Microbial diversity enhancement in a bio-electro-fenton system driven by sediment microbial fuel cells for photocatalytic PAHs degradation in antibiotics applicate soil-water systems - Muhammad Usman; Zenhua Zhao; Muhammad Adnan; Muhammad Ibrahim; Olive Mekontchou Yemele; Ghulam Abbas Ashraf; Mukhtorjon Karimov; Alisher Abduvokhidov; Naoufel Ben Hamadi (Journal of Environmental Chemical Engineering, 2026)

Food, culture, and biodiversity: An ethnogastronomic assessment of wild plants among different ethnic communities in Azerbaijan - Sayyara Ibadullayeva; Farah Amrahova; Muhammad Zafar; Salman Majeed; Nahaa M. Alotaibi; Khuzin Dinislam; Muhammad Rizwan Khan; Jushkinbek Yuldoshev; Islom Khudayberganov; Adnan Amin (International Journal of Gastronomy and Food Science, 2026)

Advances in food chemical contaminant detection and mitigation: Technological innovations, public health implications, and future directions - Muhammad Isra; Adnan Engelen; Zainudin A.K. Antuli; Riel J.J. Umboh (Food Control, 2026)

Improving groundwater level prediction based on optimized deep learning model with Coati algorithm - Rana Muhammad Adnan; Jing-Cheng Han; Mo Wang; Sandeep Samantaray; Abinash Sahoo; Sajjad Firas Abdulameer; Mohammad Al-Suwaiyan; Zaher Mundher Yaseen (Environmental Modelling & Software, 2026)

pH-switchable polyoxometalate-loaded hydrogel with intrinsic oxygen-independent singlet oxygen generation and in situ nitric oxide production for infected wound management - Cantong Sun; Zhen Zhang; Zhen Li; Muhammad Adnan Younis; Hongyu Chen; Shujun Zhang; Junle Wu; Dehao Du; Haiyan Ge; Lehao Liu; Ruiheng Li; Shengyi Dongye; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “A review on biohydrogen production through dark fermentation via the lactate pathway” [Bioresour. Technol. 454 (2026) 134726] - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Correction: Drug induced TdP risks classification assay using electro-mechanical models of human ventricle based on CiPA framework - Aulia Khamas Heikhmakhtiar; Ali Ikhsanul Qauli; Yunendah Nur Fu’adah; Muhammad Adnan Pramudito; Iga Narendra Pramawijaya; Aroli Marcellinus; Kim Yoo Seok; Frederique Jos Vanheusden; Ki Moo Lim (Toxicological Research, 2026)

Chlorophyll fluorescence signatures reveal freezing tolerance differences among new Citrus scions - Carlos Eduardo Aucique-Perez; Nazneen Qureshi; Jhon Chater; Jude Grosser; Fred Gmitter; Zafar Iqbal; Muhammad Adnan Shahid (Theoretical and Experimental Plant Physiology, 2026)

Retraction Note: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2026)

Hydrological Alterations and Soil Microbial Responses Under Prolonged Irrigation and Salinity Stress - Shakhobiddin Turdimetov; Mokhinur Musurmanova; Gulom Jurayev; Berdiyor Ixtiyor Ogli Omonboyev; Mohamed Fawzy Ramadan; Muhammad Ishtiaq Ali; Salman Majeed; Muhammad Rizwan Khan; Trobjon Makhkamov; Adnan Amin (Irrigation and Drainage, 2026)
The Mirzachol Oasis is one of the most important agroecological regions in Uzbekistan and has been subject to six decades of intensified irrigation, resulting in significant hydrological and soil changes. The impact on microbial communities below the surface is less well studied than its impact on the surface, but both affect soil health. This study addresses this gap by examining microbial communities, soil physicochemical parameters and historical irrigation data from 1960–2020 across six separate plots, including protected and irrigated plots. The results show that, due to organic matter accumulation and cultivation, extended irrigation increased microbial diversity and biogenicity in nonsaline soils (such as the U. Nasir and Yangi Hayot massifs). Nevertheless, secondary salinization disrupted nutrient cycling by suppressing functional microbial guilds, such as nitrifiers and cellulose‐degrading bacteria, in irrigated zones (e.g., the M. Uzoqov and Pakhtakor massifs). The salinization legacy reduces ecosystem stability, while older irrigated soils exhibit greater microbial resilience than recently irrigated or protected lands. Microbial activity was further influenced by seasonal variations, pH changes and groundwater fluctuations; salinity exacerbated reductions in fungal and actinomycete populations.

Retraction notice to “Environmental impacts of hazardous waste, and management strategies to reconcile circular economy and eco-sustainability” [Sci. Total Environ. 807 (2022) 150856] - Zhen Zhang; Muhammad Zeeshan Malik; Adnan Khan; Nisar Ali; Sumeet Malik; Muhammad Bilal (Science of The Total Environment, 2026)

Retraction notice to “Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China” [Sci. Total Environ. 897 (2023) 165394] - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2026)

Retraction notice to “Effective exploitation of anionic, nonionic, and nanoparticle-stabilized surfactant foams for petroleum hydrocarbon contaminated soil remediation” [Sci. Total Environ. 704 (2020) 135391] - Nisar Ali; Muhammad Bilal; Adnan Khan; Farman Ali; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

How decentralized blue-green-grey infrastructure reshapes urban drainage performance: A cost-reliability-resilience optimization framework - Mo Wang; Yijia Zhang; Chuanhao Sun; Rana Muhammad Adnan Ikram; Kexin Liu (Journal of Environmental Management, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

Advancing heat pump dryers for agricultural products processing: A critical review of drying chambers and systems - Muhammad Aqil Afham Rahmat; Ubaidah Syafiq; Muhammad Hazwan Hamzah; Nazmi Mat Nawi; Hasila Jarimi; Adnan Ibrahim (International Journal of Refrigeration, 2026)

Redox-responsive goethite-modified biochar regulates cadmium and arsenic translocation in rice via irrigation-driven iron plaque dynamics - Iftikhar Ali Ahmad; Sharjeel Haider; Muhammad Mehran; Zaryab Murad; Adnan Mustafa; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Research, 2026)

A review on biohydrogen production through dark fermentation via the lactate pathway - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Early winter precipitation variability over Pakistan and associated ENSO teleconnections - Romesa Najeeb; Irfan Ur Rashid; Rehan Ahmed; Muhammad Adnan Abid; Elham Ghasemifar; Ibrahim Alsafari (Theoretical and Applied Climatology, 2026)

Ethnobotany of desert medicinal plants and their sustainable ethnomedicinal utilization - Salman Majeed; Muhammad Zafar; Sayyara Ibadullayeva; Nahaa M Alotaibi; Sheikh Zain Ul Abidin; Muhammad Rizwan Khan; Sumreen Dawood; Khuzin Dinislam; Adnan Amin (The Science of Nature, 2026)

Pollen micromorphological variations in selected species of genus Ipomoea (Convolvulaceae) and their taxonomic significance - Aleena Gul; Muhammad Zafar; Salman Majeed; Muhammad Rizwan Khan; Samah A. Alharbi; Sayyara Ibadullayeva; Shomaila Ashfaq; Khuzin Dinislam; Adnan Amin; Samira Khudaverdiyeva (Plant Biosystems, 2026)

Biomedical applications of fungal-derived nanoparticles: bridging mycology and nanotechnology for next-generation therapeutics - Umer Rehman; Mohsin Ullah; Syed Mohammad Tauseeq Ali Shah; Muhammad Adnan; Ishtiaq Ahmad; Zabta Khan Shinwari (Plant Biosystems, 2026)

Biological and synthetic biology strategies for polystyrene degradation: mechanisms, microbial advances, and circular economy perspectives - Mehar Nazir; Asma Rehman; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Manahil Akmal; Ghazala Iram; Faiza Manzoor; Sadia Aziz; Muhammad Shehroz Zafar; Muhammad Adnan Iqbal (Biodegradation, 2026)

Integrating high-fidelity hiPSC-cardiomyocytes with AI-driven modeling for enhanced proarrhythmic risk assessment - Su-Bin Kim; Jaehun Lee; Jieun An; Ara Cho; Kun Hee Lee; Hwan Choi; Choongseong Han; Muhammad Adnan Pramudito; Ki Moo Lim; Dong-Hun Woo (Archives of Toxicology, 2026)
Cardiotoxicity remains the leading driver of drug attrition; however, its prediction remains suboptimal when conventional hERG assays and animal models are used. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) offer a human-relevant alternative that aligns with the CiPA initiative and ICH E14/S7B guidelines. This study validated an integrated platform that combines high-purity hiPSC-CMs with Artificial Intelligence (AI) to enhance the accuracy of predicting drug-induced proarrhythmic risk. Phenotypic characterization of the hiPSC-CMs demonstrated high cardiac differentiation efficiency (cTnT + > 95%) and a predominant ventricular-like identity (MLC-2 V + , 78–84%), ensuring biological relevance for ventricular arrhythmia assessment. Electrophysiological data from 28 CiPA reference compounds were collected via Multielectrode Array (MEA) to train multiple machine learning models. The Artificial Neural Network outperformed the other architectures, achieving a superior ROC-AUC of 0.982. The utility of the platform was evaluated using 12 anticancer agents. Although most drugs showed dose-dependent reductions in impedance-based viability, four compounds (Idarubicin, Erlotinib, Sunitinib, Cyclophosphamide) did not exhibit overt structural cytotoxicity. However, MEA analysis revealed significant functional perturbations, including FPDcF prolongation, in sunitinib- and erlotinib-treated samples after long-term treatment. The AI model subsequently classified these two agents as high-to-intermediate risk for Torsades de Pointes (TdP), thereby quantifying their time-dependent proarrhythmic liabilities. These findings show the platform’s ability to detect hidden functional cardiotoxicity, often missed by standard viability assays. The AI-hiPSC-CM system offers a high-throughput, early-stage safety screening tool that bridges in vitro data and clinical outcomes with a standardized risk assessment framework.

Overexpression of Cabbage BobHLH15 Enhances Cold Tolerance in Arabidopsis Thaliana - Muhammad Adnan Raza; Chen jing; Hube Ali; Song Jianghua (Journal of Plant Growth Regulation, 2026)

Investigating Charge-Carrier Dynamics in Heteroatom-Functionalized Triphenylamine Hole Transport Materials for Perovskite Solar Cells - Faiza Iram; Zobia Irshad; Riaz Hussain; Muhammad Imran; Mahmood Ahmed; Muhammad Adnan; Jae Kwan Lee (Journal of Fluorescence, 2026)

Geochemical Characterization of Saidgai and Katora Lakes for Irrigation, Drinking, and Health Risk Indices, Hindu Kush Region - Said Muhammad; Tufail Ahmad; Wajid Ali; Adnan Ali Khan; Cem Tokatli; Ashfaq Ahmad; Zafar Iqbal (Water, Air, & Soil Pollution, 2026)

Nanoencapsulated EO-based drug delivery for pest control: from chemistry to formulation design - Wajid Zaman; Asma Ayaz; Muhammad Zafar; Adnan Amin (Protoplasma, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chinese milk vetch as green manure enables simultaneous NPK fertilizer reduction while enhancing rice yield and soil fertility in subtropical systems - Tahir Shah; Muhammad Sufhan Tahir; Adnan Anwar Khan; Muhammad Fraz Ali; Sadam Khan; Muhammad Riaz; Yajun Gao; Qiang Zhu (Applied Soil Ecology, 2026)

Botulinum toxin from foodborne hazard to aesthetic and biomedical tool: mechanisms, applications, detection strategies, and future perspectives - Muhammad Adnan; Muhammad Waqar; Rais Ahmed; Haroon Afzal; Muhammad Abdullah Mueen; Urooj Qayyum; Farhang Hameed Awlqadr; Muhammad Talha Yaqoob; Sabrin R. M. Ibrahim; Gamal A. Mohamed; Iqra Rafiq; Hagar M. Mohamed (Archives of Microbiology, 2026)

Roadside dust as a vector of potentially toxic metals: an ecological and human health risk assessment in urban areas of semi-arid climatic regions - Namoos Khan; Kainat Zarin; Muhammad Adnan; Seemab Akhtar; Irfan Ullah; Javed Nawab; Nadeem Ali (Environmental Monitoring and Assessment, 2026)

Examining the Applicability of Wavelet Packet Decomposition on Statistical Models for River Stage Forecasting - Adnan Bashir; Muhammad Ahmed Shehzad (Water Resources Management, 2026)

Potential of 6-benzylaminopurine to Mitigate Salt Toxicity and Enhance Growth Performance in Tuberose (Polianthes tuberosa L.) - Muhammad Adnan Sadique; Safina Naz; Hasan Sardar (Journal of Plant Growth Regulation, 2026)

Chemical Profile, Biological Activities, Molecular Docking, and Density Functional Theory (DFT) of Cymbopogon citratus Essential Oil Extracted By Conventional and Superheated Steam Extraction Techniques - Muhammad Adnan Ayub; Fiza Bashir; Khayala Mammadova; Muhammad Talha Anjam; Muhammad Ijaz; Amjad Hussain; Mohamed Fawzy Ramadan; Fahim Arshad; Muhammad Zubair (Journal of Pharmaceutical Innovation, 2026)

Pharmaco-therapeutic modulation of the Glo1–Nrf2–RAGE functional network in chronic inflammation: polyphenols in the context of current anti-inflammatory therapy - Sajid Ali; Muhammad Saeed Akhtar; Adnan Amin; Atif Ali Khan Khalil; Wajid Zaman (Inflammopharmacology, 2026)

Integrated modelling application for assessing impacts of climate and land use change on water balance in Hadejia river basin Northwestern Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Amir Kamal Hamidon; Ruhil Amal Adnan; Shaharin Ibrahim; Muhammad Amar bin Zaudi; AbdulJalal AbdulSalam (Arabian Journal of Geosciences, 2026)

Machine Learning–Enabled Microalgae Bioprocess Optimization for Alternative Foods and Water Sustainability - Muhammad Adnan Ul Haq; Mishaal Irfan; Sana Malik; Nitiphong Kaewman; Piroonporn Srimongkol; Sirasit Srinuanpan; Shaza Y. A. Qattan; Ashwaq Hassan Alsabban; Antonio Albuquerque; Raj Boopathy; Peter Ralph (Current Pollution Reports, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Tracing subduction initiation in the Neo-Tethyan Realm: Geochemical and isotopic signatures in lherzolites of the Sapat Complex, Northern Pakistan - Zaheen Ullah; Qigui Mao; Asad Khan; Meng Zhang; Dunfeng Xiang; Wang Hao; Tehseen Zafar; Wenjiao Xiao; Adnan Khan; Muhammad Ibrar (Lithos, 2026)

Recent Advances in p-Type Nickel Oxide (NiO) for Solar-Light-Driven Photocatalytic Degradation of Organic Pollutants - Mansoor sultan; Nisar Ali; Muhammad Naseem; Shah Ihsan; Mazharul islam; Abdul kareem; Shahbaz Khan; Bakht Muhammad Khan; Fawad khan; Farman Ali; Adnan Khan; Rayya Ahmed Al Balushi; et al. (Water, Air, & Soil Pollution, 2026)

​​​​ Membrane active nanoemulgel incorporating Atorvastatin and carom seed essential oil for combating multidrug resistant microbes - Muhammad Ali; Niamat Ullah; Adnan Amin; Muhammad Zafar; Salman Majeed; Saleh AlNadhari; Sayyara Ibadullayeva; Nigar Murshal; Mukhayya Ruzieva; Islom. Khudayberganov; Khuzin Dinislam (Protoplasma, 2026)

Association of oral metoprolol exposure during heart failure hospitalization with death or readmission at 28-days and 6-months using a propensity score overlap-weighted EHR analysis - Azfar Athar Ishaqui; Emad Ali Alsaleh; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Khalid Orayj; Rayah Asiri; Sultan M. Alshahrani; Salman Ashfaq Ahmad; Narendar Kumar; Adnan Iqbal; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Improving RGB image recognition in the YOLO11n algorithm for accurate detection of tea plant diseases - Jinxian Tao; Xiaoli Li; Jingfei Zhang; Muhammad Shoaib; Muhammad Adnan Islam; Ibrar Ahmad; Yong He; Sitan Ye; Yujie Wang; Binhui Liao; Mostafa Gouda (Journal of Zhejiang University-SCIENCE B, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Rock–water interactions in the coal mining area of Dukki, Balochistan, determine the drinking and irrigation suitability of groundwater: an in-depth risk assessment - Ghazala Mohammad Ali; Muhammad Akhtar; Muhammad Faraz Bhatti; Fazal Adnan; Malik Badshah; Ghayas Haider Sajid; Ghulam Haider (Environmental Geochemistry and Health, 2026)

The biological synthesis of iron oxide nanomaterials and their possible physiological and biochemical toxicities in Cyprinus carpio - Nadia Bibi; Nishita Narwal; Muhammad Anees; Huma Ayub; Mian Adnan Kakakhel; Tawaf Ali Shah; Ashraf Khalifa; Imran Ibrahim Shaikh (Ecotoxicology, 2026)

Stacking Ensemble Machine Learning for Cardiac Safety Assessment Using hiPSC-CM MEA Data - Muhammad Adnan Pramudito; Yunendah Nur Fuadah; Yoo Seok Kim; Ki Moo Lim (Annals of Biomedical Engineering, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

Molecular insights into HPV-16 L2 capsid protein and inhibitor screening study - Saima Younas; Atiqa Nosheen; Muhammad Abdul Qayyum; Hafiza Ayesha Malik; Sadia Manzoor; Rabia Arooj; Nazim Hussain; Qurban Ali; Muhammad Arshad Javed; Daoud Ali; Adnan Iqbal (In Silico Pharmacology, 2026)

Antimicrobial and antioxidant activities of Tetracera macrophylla Hook.f. & Thomson leaf extracts: insights from Q-ToF-LCMS, pharmacokinetics and molecular docking approach - Qamar Uddin Ahmed; Muhammad Akmal Hakim Ab Rahim; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Nurul Hidayah Mohd Rosedi; Murni Nazira Sarian; Taslima Begum (Natural Product Research, 2026)

Heavy metal pollution in soils affected by copper mining and geospatial analysis in the Ophiolite belt of Pakistan - Muhammad Adnan; Baohua Xiao; Muhammad Ubaid Ali; Qiao Han (Journal of Environmental Chemical Engineering, 2026)

Immobilization and stabilization nexus of bio-waste derived biochar towards potentially toxic elements in vegetables: A deterministic and probabilistic human health risk assessment - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab (Biomass and Bioenergy, 2026)

Rising Waters: Designing Climate-Resilient Urban Drainage System - Muhammad Adnan; Fayaz Ahmad Khan; Afed Ullah Khan; Basir Ullah (Water Conservation Science and Engineering, 2026)

Stem anatomical microcharacters and morphology as diagnostic botanical markers in Euphorbiaceae species - Sehrish Rubab; Salman Majeed; Sumreen Dawood; Muhammad Zafar; Modhi O. Alotaibi; Sayyara Ibadullayeva; Fakhra Bibi; Yusra Khan; Adnan Amin (The Science of Nature, 2026)

Seismotectonic Analysis of Pabbi Blind-Thrust in the NW Himalayan Foreland: Evidence from the 2024 Kharian Earthquake - Mohammad Tahir; Bilal Saif; Raja Adnan Habib; Farhan Javed; Muhammad Zafar Iqbal; Talat Iqbal; Nasir Mahmood; Najeeb Ahmed (Pure and Applied Geophysics, 2026)

Development of cytarabine-loaded pH-responsive polymeric hydrogel: an in vitro and in vivo evaluation - Shaheer Khalid; Sharjeel Adnan; Asif Mahmood; Rai Muhammad Sarfraz; Hira Ijaz; Muhammad Farooq; Bilal Haroon (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Stage-specific endophytic colonization of maize by Metarhizium anisopliae (Clavicipitaceae, Hypocreales): effects on Spodoptera Frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) fitness and plant growth - Muhammad Adnan; Muhammad Irfan Ullah; Muhammad Arshad; Emaan Sajid; Lamya Ahmed Alkeridis; Laila A. Al-Shuraym; Ohud Muslat Aharthy; Seham Sater Alhelaify; Hosny Kesba; Samy Sayed (Journal of Plant Diseases and Protection, 2026)

The ameliorative effects of glutamic acid-capped hydroxyapatite nanoparticles on the physio-chemical parameters of sunflower (Helianthus annuus L.) under induced salt stress - Seemab Akhtar; Irfan Ullah; Muhammad Adnan; Javed Nawab; Rehman Ullah (Journal of Crop Science and Biotechnology, 2026)

Spatial distribution of heavy metals and ecological risk assessment in Sea buckthorn across high-mountain landscapes of HKH ranges, Gilgit-Baltistan, Pakistan - Kamran Ali Khan; Faridullah Faridullah; Adnan Ahmad Tahir; Muhammad Irshad; Shaxina Tuyg’unovna Shukurova; Farhan Hafeez; Arshad Mahmood Abbasi (Environmental Geochemistry and Health, 2026)

Silver nanoparticles in water disinfection: a comprehensive overview on their mechanisms, benefits, and limitations - Muhammad Shehroz Zafar; Sana Ejaz; Farhan Ahmad; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Faiza Manzoor; Sadia Aziz; Saima Iqbal; Muhammad Adnan Iqbal (Archives of Microbiology, 2026)

Agriculture, industry, and economic growth as determinants of carbon emissions in climate hotspots: evidence from dynamic causal analysis - Amir Mustafa; Naeem Ahmed; Munib Ahmed; Muhammad Adnan Bashir (Environment, Development and Sustainability, 2026)

Improving In Silico Cardiac Safety Prediction by Consensus Averaging of Transmural Ventricular Cell Models - Nurul Qashri Mahardika T; Ali Ikhsanul Qauli; Yunendah Nur Fuadah; Aulia Khamas Heikhmakhtiar; Muhammad Adnan Pramudito; Ariyadi; Aroli Marcellinus; Yoo Seok Kim; Ki Moo Lim (Annals of Biomedical Engineering, 2026)

Enhance soil phosphorus availability via the growth and decomposition of green manure crops in drylands - Gaohai Han; Rana Muhammad Ammar Asghar; Adnan Anwar Khan; Yupei Chen; Jiarong Wang; Shijie Wei; Chenxi Liu; Zhiqi Li; Zhaohui Wang; Donglin Huang; Xiaomin Wei; Weidong Cao; et al. (Soil and Tillage Research, 2026)

Biochar pyrolysis temperature determines the efficacy of 3, 4-dimethylpyrazole phosphate (DMPP) in reducing N2O emissions from low cadmium-contaminated paddy soil - Muhammad Laeeq Ur Rehman HASHMI; Muhammad Zia Ur Rahman HASHMI; Yasir HAMID; Bilal HUSSAIN; Tang SHENG; Wenjie LIU; Adnan ARSHAD; Tingqiang LI (Pedosphere, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Unveiling the complex impact of microplastics on environmental health, ecosystems, and humans - Xianjin An; Jiajia Yao; Muhammad Adnan; Huicheng Fu; Yaqin Zhang; Wei Li; Lihui An (Journal of Environmental Management, 2026)

Root traits and rhizosphere responses as emerging bioindicators of microplastic pollution in agricultural soils: A review - Qudsia Saeed; Xiankai Lu; Zia Ur Rahman Farooqi; Abdul Ghafoor; Muhammad Naveed; Nimra Maqsood; Hafiz Abdul Kareem; Adnan Mustafa (Environmental Research, 2026)

Drug induced TdP risks classification assay using electro-mechanical models of human ventricle based on CiPA framework - Aulia Khamas Heikhmakhtiar; Ali Ikhsanul Qauli; Yunendah Nur Fu’adah; Muhammad Adnan Pramudito; Iga Narendra Pramawijaya; Aroli Marcellinus; Kim Yoo Seok; Frederique Jos Vanheusden; Ki Moo Lim (Toxicological Research, 2026)

A comparative analysis of tsunami flow through emergent and submerged coastal vegetation using numerical simulation - Syed Muhammad Ahmad Bukhari; Naveed Anjum; Saad Abbas; Adnan Shahid; Abdul Basit Bukhari; Ghufran Ahmed Pasha (Natural Hazards, 2026)

Synergistic Effect of Biochar and Bacillus Subtilis on the Development of Colletotrichum Graminicola in Maize - Nimra Nadeem; Adnan Akhter; Waheed Anwar; Tehmina Anjum; Muhammad Khurshid; Nasir Ali; Sana Javed; Hibba Arshad (Journal of Soil Science and Plant Nutrition, 2026)

Brassinosteroids: Key Players to Improve Drought Tolerance and Crop Productivity - Muhammad Inzamam-UL-Haq; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Sezai Ercişli; Uthman Balgith Algopishi; Fatima M. Abbas; Mohamed Hashem; Muhammad Mahmood Iqbal; Muhammad Umair Hassan (International Journal of Plant Production, 2026)

Sulfur-Coated Urea Improves Rice productivity, Nitrogen Use Efficiency, and Soil Nitrogen Dynamics Under Alternate Wetting and Drying System - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Muhammad Bilal Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Umair Hassan; Uthman Balgith Algopishi; Mohamed Hashem; Sezai Ercişli (International Journal of Plant Production, 2026)

Impact of Drought on Agricultural Ecosystems, Biomass and Carbon Uptake in the Northern Part of Bangladesh Using Remote Sensing and Weather Station Data - Nur Hussain; Md Adnan Rahman; Muhammad Rezaul Rakib; Md. Nurul Islam; Md Kamruzzaman (Remote Sensing in Earth Systems Sciences, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Automated geolocalization of vehicles from UAV footage: evaluating measurement precision of object detection and segmentation methods - Muhammad Waqas Ahmed; Muhammad Adnan; Muhammad Ahmed; Davy Janssens; Geert Wets; Afzal Ahmed; Wim Ectors (Applied Geomatics, 2026)

Simultaneous quantification of hydroxycinnamate derivatives and antioxidant activity of Ziziphus oxyphylla Edgew. leaf methanolic extract - Surriya Naheed; Muhammad Wajid; Afsheen Ehsan; Khalid Hussain; Gulzar Muhammad; Naureen Shehzadi; Muhammad Tanveer Khan; Imran Ahmad; Adnan Ashraf (Natural Product Research, 2026)

Investigation of Metabolites and Mineral Content in Blood Serum of Dairy Cows of the Simmental Breed in Samsun Province During the Transition Period - Neslihan Ormancı; Bora Bölükbaş; Muhammad Waqas; Mustafa Salman; Rıfat Pak; Doğukan Topal; Adnan Vehapoğlu (Biological Trace Element Research, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Intelligent transformation of the tea industry: Artificial intelligence applications in management, harvesting, and processing - Xuechen Zhang; Sitan Ye; Yujie Wang; Mostafa Gouda; Yan Hu; Muhammad Adnan Islam; Yong He; Xiaoli Li (Trends in Food Science & Technology, 2026)

Novel Styrofoam-sludge biochar for Pb and Zn adsorption: Bioavailability and reduction in maize-cultivated contaminated soils - Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Ruilian Yu; Gongren Hu; Balal Yousaf; Sajid Ali; Muhammad Adnan; Cheng Liping; Xiangliang Pan; Ming Hung Wong (Journal of Cleaner Production, 2026)

Understanding green house gases emission dynamics from forest fires in Thailand using predictive models - Fahad Shahzad; Kaleem Mehmood; Shoaib Ahmad Anees; Muhammad Adnan; Khadim Hussain; Waseem Razzaq Khan; Munawar Shah; Punyawi Jamjareegulgarn; Manuela Oliveira; José G. Borges (Global and Planetary Change, 2026)

Synergistic role of microbes and wetland plants in an advanced-acclimatized constructed wetland for enhanced removal of heavy metals - Adnan Abbas; Muhammad Ahmad; Maryam Yousaf; Linghui Pan; Dayong Xu (Gondwana Research, 2026)

Hyperbranched aromatic polyamide-modified nanofiltration membranes for improved water permeability and salt rejection - Muhammad Adnan Akram; Shengchao Zhao; Mengting Wang; Munir Hussain; Q. Jason Niu (Desalination, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

Influence of flow characteristics on thermal energy storage during Paraffine wax melting process - Adnan Muhammad; Hui Wang; Wang Yanlu; Khan Jamil; Cao Xiaxin (Annals of Nuclear Energy, 2026)

Analysis of multiple blockages in a coolant channel of IAEA research reactor using CFD - Muhammad Abdullah; Muhammad Nadeem; Arif; Adnan Hamid (Annals of Nuclear Energy, 2026)

Eco-Friendly Gum Arabic–Essential Oil Coatings for Decay Control and Quality Preservation of Pomegranate Fruit During Storage - Muhammad Waqar Alam; Sumreen Anjum; Mubeen Sarwar; Adnan Mukhtar; Akhtar Hameed; Tanveer Hussain; Tauhid Iqbal (Applied Fruit Science, 2026)

Beyond limitations: Integrating advanced analytical techniques for a new era of soil organic matter characterization - Adnan MUSTAFA; Qudsia SAEED; Lasisi H. TOBILOBA; Yakov KUZYAKOV; Muhammad NAVEED; Mohammad T.K. NEZHAD; Muhammed M. IBRAHIM; Jan FROUZ; Martin BRTNICKY; Jiri KUCERIK; Xiankai LU (Pedosphere, 2026)

Considerable potential for artificial ice reservoirs in the Mongolian Altai mountains to mitigate the impact of climate change on water security in arid western Mongolia - Zolbayar Jargalsaikhan; Batsuren Dorjsuren; Otgonbayar Demberel; Altanbold Enkhbold; Dashlkham Batmunkh; Muhammad Adnan; Hongkai Gao (Cold Regions Science and Technology, 2026)

Holistic review on Paenibacillus: The multifunctional genus in heavy metal detoxification, pesticide degradation, and abiotic stress mitigation for Sustainable Agriculture - Izhar Khan; Nadeem Ullah; Haris Maqbool; Adnan Hashmi; Basit Khan; Afnan Khalid; Iffat Naz; Najeeba Parre Paker; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Plant and Soil, 2026)

Natural products in medicinal chemistry: targeting inflammatory pathways with plant-derived compounds - Adnan Amin; Muhammad Saeed Akhtar; Atif Ali Khan Khalil; Sajid Ali; Wajid Zaman (Medicinal Chemistry Research, 2026)

Spatial distribution, source characterization, and risk indices of heavy metals pollution in the sediments of the Hindu Kush Lacustrine ecosystem - Said Muhammad; Zeeshan Ahmad; Cem Tokatli; Adnan Khan; Zafar Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2026)

Experimental Study of Local Scour Around Two Compound Piles in Tandem, Side-by-Side and Staggered Arrangements Under Steady Current - Muhammad Adnan; Ming Zhao; Helen Wu; Adnan Munir; Vatsal Dhamelia (Journal of Marine Science and Engineering, 2025)
Scour around two compound piles (CPs) in tandem, side-by-side (SBS), and staggered arrangements is investigated through experiments. Each CP has a larger diameter foundation, which is partially buried, and a smaller diameter top part with a diameter ratio of 0.5. The exposed height of the foundation is equal to its diameter. Experiments are conducted for gap ratios from 1 to 3. Due to the shadowing effect from the upstream CP, the downstream CP in the tandem arrangement has shallower scour depth and its most downstream point has deposition at an early stage. In the SBS arrangement, the scour does not have much difference from that of a single CP, but the inner side of each CP has a slightly deeper scour hole than the outer side of each CP and scour hole became independent at gap ratio of 3. In the staggered arrangement, the shadowing effect from the upstream CP was experienced by the downstream CP when G/D = 1, but not 1.5 and 3.

An Adaptive Nudging Scheme with Spatially Varying Gain for Improving the Ability of Ocean Temperature Assimilation in SPEEDY-NEMO - Yushan Wang; Fei Zheng; Changxiang Yan; Muhammad Adnan Abid (Journal of Marine Science and Engineering, 2025)
Nudging remains a cost-effective data assimilation technique in coupled climate models, yet conventional schemes with fixed spatial strengths struggle to represent heterogeneous ocean processes. This study introduces an adaptive nudging framework in which a spatially varying gain matrix dynamically balances model and observational errors, providing a more physically consistent determination of nudging coefficients. Implemented in the SPEEDY-NEMO coupled model, the method is systematically evaluated against a traditional latitude-dependent scheme. Results show substantial improvements in subsurface temperature assimilation across key regions, including the Niño3.4, tropical Indian Ocean, North Pacific, North Atlantic, and northeastern Pacific. The most pronounced gains occur above and within the thermocline, where strong stratification renders fixed nudging strengths inadequate, yielding a 20–30% reduction in RMSE and a 30–50% increase in correlation. In mid- to high-latitude regions, improvements extend to greater depths, consistent with deeper thermocline structures. The adaptive framework corrects both systematic bias and variance, enhancing not only the mean state but also variability representation. Additional benefits are found in salinity, currents, and sea surface height, demonstrating that spatially adaptive nudging provides a more effective and practical alternative for improving ocean state estimation in coupled models.

Laboratory and greenhouse endophytic colonization of tomato by three entomopathogenic fungal isolates for the management of Tetranychus urticae and field efficacy trials - Waqas Wakil; Maria C. Boukouvala; Nickolas G. Kavallieratos; Aqsa Naeem; Syed Adnan Haider; Muhammad Usman Ghazanfar; Pasco B. Avery (Crop Protection, 2025)

GTG-ACO: Graph Transformer Guided Ant Colony Optimization for learning heuristics and pheromone dynamics for combinatorial optimization - Abrar Rahman Abir; Muhammad Ali Nayeem; M. Sohel Rahman; Md Adnan Arefeen (Swarm and Evolutionary Computation, 2025)

Leveraging green roof technology: Stakeholder analysis of sustainable urban landscape in the developing regions of South Asia - Mehak Shehzad; Adnan Younis; Sabir Aziz; Muhammad Khizar; Noor ul Ain; Muhammad Asad Shabbir (Land Use Policy, 2025)

Chemical speciation and transformation of heavy metals in soil and groundwater: Implications for ecotoxicology and remediation - Qiao Han; Guoyang Fu; Kewu Liu; Muhammad Adnan; Songtao Liu; Mingya Wang; Fengcheng Jiang; Mingshi Wang (Journal of Environmental Chemical Engineering, 2025)

Application of novel deep learning model for high-frequency water quality prediction in multi-station river networks - Yuchen Wang; Jing-Cheng Han; Yang Zhou; Xiuquan Wang; Rana Muhammad Adnan Ikram; Xu Zhao; Yuefei Huang (Journal of Environmental Chemical Engineering, 2025)

Physicochemical, Organoleptic and anti-obesity effects of water melon peel powder incorporation into chapatti - Sania Niaz; Samreen Ahsan; Muhammad Farhan Jahangir Chughtai; Tariq Mehmood; Muhammad Adil Farooq; Madiha Wali; Adnan Khaliq (Food and Humanity, 2025)

Sacrificial agent-free H2O2 production driven by S-scheme photocatalysis over hierarchical ZnO/UiO-66-NH2 heterojunction - Muhammad Adnan Qaiser; Jinhe Li; Wei Ren; Shahid Khan; Syed Bilal Ahmed; Waqar Ahmad Qureshi; Mohamed Hussein Abdurahman; Weikang Wang; Qinqin Liu (Chemical Engineering Journal, 2025)

Green approaches for modifying lignocellulosic features: Recent advances in reducing recalcitrance for sustainable bioethanol production - Muhammad Adnan; Adeel Ahmed; Muhammad Rafiq; Nasim Ullah; Ali Ahmad; Muhammad Sarfraz; Raza Ullah; Muzamil Ahmad; Bing Yu; Hailin Cong (Biomass and Bioenergy, 2025)

Evaluation of Polystyrene Biodegradation: Characterization of biodegradation kinetics of Rhizopus oryzae Strain NA1 at Mesophilic Temperature - Sadia Mehmood Satti; Naima Atiq; Asim Abbasi; Safia Ahmed; Muhammad Adnan Shereen; Aftab Ahmad; Abeer Hashem; Najla A. Alshaikh; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (Water, Air, & Soil Pollution, 2025)

Assessing hazardous flash flood susceptibility using multivariate zonation mapping techniques in Pishin District, Balochistan province of Pakistan - Muhammad Ashraf; Qahir Shah; Adnan Arshad; Ghulam Murtaza (Natural Hazards, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Exploring ethnoveterinary practices: a comprehensive study of medicinal plants in Bannu District, Khyber Pakhtunkhwa, Pakistan - Waseem Ahmed Khattak; Malka Saba; Minhas Elahi; Muhammad Anas; Qurban Ali Magsi; Rabia Tabassum; Adnan Khattak; Muhammad Majeed; Murad Muhammad (Genetic Resources and Crop Evolution, 2025)

Molecular detection and prevalence of colistin-resistant Escherichia coli in poultry and humans: a one health perspective - Muhammad Najam Ul Huda; Muhammad Zubair Shabbir; Adnan Hasan Tahir; Awais Ali Ahmad; Umar Bin Zahoor; Waqas Ahmad; Ali Raza; Farhan Afzal; Abdur Rauf Khalid; Muhammad Abu Bakr Shabbir (Brazilian Journal of Microbiology, 2025)

P-solubilising bacteria and P-cycling genes drive soil P transformation during green manure decomposition - Adnan Anwar Khan; Yupei Chen; Rana Muhammad Ammar Asghar; Imran Azeem; Tahir Shah; Weidong Cao; Dabin Zhang; Yajun Gao (Agriculture, Ecosystems & Environment, 2025)

Comparative study of extraction methods and process parameters of polyphenolic content obtained from Celosia argentea L. Flower for herbal sunscreen - Humaira Arshad; Adnan Afzal; Arifa Mehreen; Faiza Shakoor; Valisher Sapayev Odilbek Uglu; Saima Qadeer; Samiyah Tasleem; Rana Muhammad Kamran Shabbir; Mukhayya Djumaniyazova (Natural Product Research, 2025)

A lightweight georeferencing workflow for dynamic UAV footage using feature-matching and minimal drone metadata - Muhammad Waqas Ahmed; Muhammad Adnan; Muhammad Ahmed; Davy Janssens; Geert Wets; Afzal Ahmed; Wim Ectors (Remote Sensing Applications: Society and Environment, 2025)

Low frequency electrostatic wave dynamics in the subsolar magnetosheath of Venus: A theoretical framework with multi-ion and suprathermal electrons - Adil Murad; Muhammad Adnan; Shahida Parveen; Ikramullah; Fida Younus Khattak (Planetary and Space Science, 2025)

Synergistic PMS activation by SnBi@ZrC under visible light for enhanced organic pollutant removal - Rana Mohsin Ali; Jie Wang; Tianhong Zhou; Yue Tian; Muhammad Usman; Hamza Khaliq; Muhammad Adnan; Zunaira Nasir; Ghulam Abbas Ashraf; Yusuke Yamauchi (Journal of Water Process Engineering, 2025)

Study on the effect of alginate coated Ca-Fe bimetallic composite biochar microspheres on the removal of short-chain PFAS - Binglu Teng; Zhenhua Zhao; Jiangxuan Wu; Liling Xia; Yuanchi Wang; Hailong Wang; Olive M. Yemele; Muhammad Adnan (Environmental Research, 2025)

Monodispersed flower-like Mo2V2C3T MXenes synthesized via Lewis acid molten salt etching with exceptional capacity retention for lithium-ion batteries - Mugilan Narayanasamy; Infanta Diana Michael; Balasubramaniam Meichandiran; Abdul Rehman Akbar; Adnan Muhammad; Misbah Mushtaq; Tadhg Kennedy (Chemical Engineering Journal, 2025)

Liquid biopsy in breast cancer: clinical implications of ctDNA and CTCs in diagnosis, treatment and monitoring - Muhammad Umer Khan; Arooj Khawar; Muhammad Ikram Ullah; Muhammad Adnan Shan; Luca Falzone; Massimo Libra; Graziana Spoto; Javad Sharifi-Rad; Daniela Calina (Molecular and Cellular Biochemistry, 2025)

Identifying the optimum irrigation strategies to maximize canola yield and profitability under climate change in Guanzhong Plain, China - Qaisar Saddique; De Li Liu; Ali Ajaz; Bin Wang; Xiaobo Gu; Muhammad Adnan; Puyu Feng; Yunfei Wang; Yufeng Zou; Huanjie Cai (Irrigation Science, 2025)
Climate change has a substantial impact on Chinese canola production, introducing a high level of uncertainty regarding future climatic conditions and their potential impact on canola production and gross margins. This study focused on identifying the optimal irrigation strategy to enhance the profitability of canola production in the Guanzhong Plain under future climate change conditions. In this study, we used the calibrated Agricultural Production Systems sIMulator (APSIM)-Canola model with the downscaled daily climate projections from 27 general circulation models (GCMs). These simulations were conducted under two Shared Socio-economic Pathways scenarios (SSP245 and SSP585) to assess the impact of climate change on canola phenology, rainfed and irrigated crop yield. We also conducted a gross margin analysis to assess the profitability dynamics of supplying irrigation to rainfed canola crop. An increase in rainfed canola yield was observed for all simulation periods, with an average increase of 11%, 15%, and 17% for the 2030s, 2060s, and 2090s, respectively. Supplementary irrigation using a threshold of 10–60% of plant available water capacity (PAWC) was found to be effective. Overall, it led to a 28% increase in yield for rainfed and an 85% improvement in gross margin. Beyond the threshold of 60% PAWC, additional irrigation did not result in statistically significant increases in yield and gross margin. We identified the optimal amount of irrigation for achieving maximum water productivity (WP) ranges from 85 to 150 millimeters. By avoiding irrigation when the soil’s plant available water capacity (PAWC) is over 60%, up to 44% of water can be saved. These findings could be useful for policymakers and farmers in planning for sustainable and enhanced canola production in the region.

Efficacy and safety of cyclosporine in colitis: An updated meta-analysis of randomized control trials (1998 to 2024) - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Shaista Aslam; Adnan Haider; Muneeb Ullah; Jin-Wook Yoo; Rida Fatima Saeed; Muhammad Naeem (Inflammopharmacology, 2025)

A machine learning assisted approach to classify rose species and varieties with laser induced breakdown spectroscopy - Maryam Manzoor; Muhammad Faheem; Muhammad Nadeem; Guljan Shreen; Faisal Hayat; Adnan Younis; Yasir Jamil (Analytica Chimica Acta, 2025)

Spatio-temporal variability study of Shigar Basin Glaciers, Central Karakoram Region, Pakistan - Salman Mustafa; Faisal Rehman; Adnan Shafiq Rana; Tahir Azeem; Omar Riaz; Muhammad Fahad Ullah; Jamil Siddique; Faisal Rehman (Environmental Monitoring and Assessment, 2025)

DFT, GC-MS analysis and biological evaluation of Limbarda crithmoides L. Dumort essential oil; an important edible halophyte grown in Pakistan - Muhammad Iltaf; Shah Iram Niaz; Muhammad Kashif Majeed; Muhammad Saleem; Mubarak Shah; Muhammad Ali; Syed Shakeel Abbas; Adnan Amin (Natural Product Research, 2025)

First report of Alternaria alternata causing leaf blotch and fruit spot of apple in Pakistan - Sami Ullah; Samiullah; Naseer Ahmed; Muhammad Kamran; Muhammad Ibrahim; Safdar Ali; Adnan Kashif (New Zealand Journal of Botany, 2025)

Towards greening smart cities: Navigating net zero carbon in construction by 2050 through sustainable practices, innovation climate, and management support - Muhammad Javid Nawaz; Aymen Sajjad; Abdul Haseeb Tahir; Muhammad Adnan; Muhammad Umer; Huaming Song (Sustainable Cities and Society, 2025)

Co-utilization of green manure with straw return enhances the stability of soil organic carbon by regulating iron-mediated stabilization of aggregate-associated organic carbon in paddy soil - Muhammad Mehran; Li Huang; Mingjian Geng; Yafen Gan; Jinyun Cheng; Qiang Zhu; Iftikhar Ali Ahmad; Sharjeel Haider; Adnan Mustafa (Soil and Tillage Research, 2025)

Comprehensive investigation of the smouldering characteristics of hemic peat under varying moisture conditions and the combined influence of wind velocity and direction - Nor Azizah Che Azmi; Ahmad Safuan A Rashid; Nazirah Mohd Apandi; Abd Wahid Rasib; Mohd Nazri Mohd Nasir; Adnan Zainorabidin; Mohamad Sofi Mohamed; Muhammad Amir Mat Shah; Diana Che Lat; Afiqah Ismail (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Antioxidant activity and Structural-Activity Relationship (SAR) study of stilbenoids isolated from the stem bark of Anisoptera laevis (Dipterocarpaceae) - Noorazlina Adnan; Aisyah Salihah Kamarozaman; Siti Zakirah Azahar; Nik Fatini Nik Azmin; Muhammad Sulaiman Mohd Johari; Norizan Ahmat (Phytochemistry Letters, 2025)

Enhanced cadmium removal from wastewater using ZnO/MgO coated organo-mineral composites of biochar and bentonite: A comparative adsorption study - Saqib Bashir; Yurong Wang; Ziyao Li; Liqin He; Muhammad Adnan; Xingxiang Wang (Journal of Water Process Engineering, 2025)

Corrigendum to: “Substitution of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China” [J Hazard Mater 465 (2024) 1–14 133118] - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2025)

Optimization of superheated steam extraction of essential oil from Citrus limetta Peel by response surface methodology - Muhammad Adnan Ayub; Ambreen Fatima; Yousef M. Alanazi; Muhammad Asif Javaid; Abdullah Ijaz Hussain; Muhammad Shahid; Muhammad Zubair; Kim D. Thomspon (Innovative Food Science & Emerging Technologies, 2025)

Seasonal and interannual variability of Karakoram glacier surface albedo from AVHRR-MODIS data, 1982–2020 - Fuming Xie; Shiyin Liu; Tobias Bolch; Yu Zhu; Yongpeng Gao; Shucheng Tan; Muhammad Mannan Afzal; Adnan A. Tahir; Yiyuan Shen; Jinyue Wei; Kunpeng Wu; Muhammad Saifullah (Global and Planetary Change, 2025)

Cobalt-catalyzed reductive cross-coupling: a review - Shamoon Hassan; Muhammad Bilal; Shehla Khalid; Nasir Rasool; Muhammad Imran; Adnan Ali Shah (Molecular Diversity, 2025)

Unraveling the Biology and Integrated Management Strategies for Tobacco Beetle (Lasioderma serricorne) in Stored Tobacco: A Comprehensive Review - Ayesha Younas; Muhammad Adnan Bodlah; Yasir Niaz; Alishbah Mohsin; Aleena Kanwal; Imran Bodlah (Journal of Crop Health, 2025)

Comparative Analysis of the Efficiencies of Two Low Cost Adsorbents for Carbon Dioxide Capture - Sayyaf Yousaf; Haris Abdullah Noor; Muhammad Wajid Ullah; Alireza Noorpoor; Adnan Ahmad Tahir; Maria Siddique; Romana Khan (International Journal of Environmental Research, 2025)

Potential toxicological assessment of 4-Methylimidazole (4-MEI) in Ctenopharyngodon idella; LC50 determination, acute and sublethal effects on physiological, immunological, and histopathological indicators - Muhib Zaman; Amina Zuberi; Waqar Younas; Muhammad Noorullah; Faisal Ahmad Lodhi; Adnan Khan (Fish Physiology and Biochemistry, 2025)

Facile construction of chitosan-ternary metal selenide biopolymer-based composite for photocatalytic degradation of petroleum derive sunset yellow and acid black azo-dyes using response surface methodology RSM - Tariq Aziz; Muhammad Farhan; Adnan Khan; Nisar Ali; Javeed Azam; Sumeet Malik; Sarmad Ali; Nauman Ali; Hamayun Khan; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; Thuraya Al-Harthy (Environmental Science and Pollution Research, 2025)

New paradigms to evaluate the stratigraphy for the geological and geoarchaeological prospects of the upper and post-Siwaliks in the Soan Valley, Upper Indus Basin, Pakistan - Nadir Fawad; Daidu Fan; Taixun Liu; Anne Dambricourt Malassé; Muhammad Kamran; Qazi Adnan Ahmed; Fahad Ali (Quaternary International, 2025)

Cerium-doped bismuth-oxy chloride microspheres encased in conductive carbon support with tuned visible-light activity and delayed charge carrier recombination for the degradation of organic compounds - Gehad M. Subaiea; Adnan Rasheed; Ahmed Alobaida; Nasrin E. Khalifa; Hemat E. El-Horany; Muhammad Farooq Warsi; Ahmed A. Katamesh (Journal of Water Process Engineering, 2025)

Mechanisms of toxic metal(loid) migration in the slag-soil-groundwater continuum: Geochemical evidence from an abandoned industrial complex - Peng Zhao; Haili Zhang; Xuefeng Yang; Haiyan Wang; Muhammad Adnan; Yunlong Wu; Yuhui Liu; Lin Guo; Hai-Bo Qin; Baohua Xiao; Shengguo Xue (Journal of Cleaner Production, 2025)

Ultrasound-assisted dispersive solidified floating organic drop microextraction based on a novel thiazolyl azo deep eutectic solvent for antimony determination in water and food samples - Ebaa Adnan Azooz; Shaimaa Rahim Hussein; Ibrahim A. Naguib; Muhammad Farooque Lanjwani; Mustafa Tuzen (Food Chemistry, 2025)

Ultrasmall polylysine dendrimer nanodots for glutathione-responsive targeted chemotherapy and enhanced photodynamic/immunotherapy of metastatic cancer - Ruibing An; Qianting Zhang; Dehao Du; Cantong Sun; Shujun Zhang; Junle Wu; Muhammad Adnan Younis; Haiyan Ge; Kaiqi Wang; Muhammad Rizwan Younis; Jian Dong (Chemical Engineering Journal, 2025)

Impact of Reconditioning Treatment at Different Temperatures on Potato Cultivars Stored Under Cold Conditions - Adnan Amjad; Aziz Mouhaddach; Hanane Latifi; Rabia Mehboob; Tusneem Kausar; Mohamed Bouhrim; Ramzi A. Mothana; Omar M. Noman; Farzana Siddique; Muhammad Bilal; Shehnshah Zafar; Ashiq Hussain (Potato Research, 2025)

Crop Residue Management for Soil Health and Environmental Sustainability: A Comprehensive Review - Sadia Babar Baloch; Shahzaib Ali; Jaroslav Bernas; Petr Konvalina; Muhammad Naveed; Faryal Babar Baloch; Zameer Hussain Jamali; Tomáš Lošák; Hynek Roubík; Abdul Ghafoor; Mohsin Mehmood; Adnan Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Foliar-Application of Proline Mitigates Salinity Stress in Two Maize (Zea mays L.) Genotypes: A Comparative Study of Growth, Physiology, Chlorophyll Fluorescence, and Ionic Composition - Tayyaba Naz; Muhammad Mazhar Iqbal; Iftikhar Ahmad; Muhammad Adnan Sohail; Shazia Iqbal; Aftab Jamal; Luis Alfonso Rodriguez-Paez; Marcelo F. Pompelli (Journal of Plant Growth Regulation, 2025)

Modulation of inflammatory and oxidative stress pathways by polyphenol-rich Pleurospermum candollei extract in carrageenan-induced paw edema in rats - Mehreen Fatima; Muhammad Rashid Khan; Motrih Al-Mutiry; Mitesh Patel; Nawaf Alshammari; Mohd Adnan (Inflammopharmacology, 2025)

Predicting water quality variables using gradient boosting machine: global versus local explainability using SHapley Additive Explanations (SHAP) - Khaled Merabet; Fabio Di Nunno; Francesco Granata; Sungwon Kim; Rana Muhammad Adnan; Salim Heddam; Ozgur Kisi; Mohammad Zounemat-Kermani (Earth Science Informatics, 2025)

Advancing forest fire prediction: A multi-layer stacking ensemble model approach - Fahad Shahzad; Kaleem Mehmood; Shoaib Ahmad Anees; Muhammad Adnan; Sultan Muhammad; Ijlal Haidar; Jamshid Ali; Khadim Hussain; Zhongke Feng; Waseem Razzaq Khan (Earth Science Informatics, 2025)

Computational Investigation of Hull Vane Effects on Resistance and Propulsive Performance of a Patrol Vessel - Muhammad Irfan Shahmi bin Abdul Ra’uf; Iwan Mustaffa Kamal; Nor Adlina Othman; Yaseen Adnan Ahmed (Journal of Marine Science and Engineering, 2025)
This study investigates the effect of Hull Vane® on the total resistance and propulsion performance of a patrol vessel using computational fluid dynamics (CFD). Utilizing SHIPFLOW software, multiple simulations were conducted to evaluate how Hull Vane® position and angle of attack influence hydrodynamic performance. A patrol vessel hull form the MAXSURF’s library was selected to investigate resistance and propulsive performance. Nine (9) configurations (named Cases A to I) of the Hull Vane® were examined based on variations in longitudinal position and angle of attack. A grid independence study was conducted to determine the optimal mesh configuration. Validation was performed using the Holtrop–Mennen power prediction method and MAXSURF. According to this study, results indicate that Hull Vane® configurations significantly reduce total resistance and delivered power at higher vessel speeds, with the best improvement in resistance occurring in Case C and in propulsion power in Case B. Propulsive efficiency was maximized in Case E. Furthermore, the study also demonstrates the potential of Hull Vane® as a practical retrofit for enhancing naval vessel performance and reducing energy consumption.

Hollow cavity engineering of MOF-derived hierarchical nitrogen-doped In2O3@carbon for efficient photocatalytic degradation of tetracycline hydrochloride - Raza Ullah; Muhammad Rafiq; Alamgir; Abdul Qadir; Adeel Ahmed; Muhammad Fayaz; Muhammad Adnan; Nasim Ullah; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Novel MAX-phase Nb2AlC@Biochar: A dual-functional peroxymonosulfates activator for antibiotics and dyes degradation via Nb4+/Nb5+ redox switches; DFT insight and mechanistic elicitation - Muhammad Adnan; Zhenhua Zhao; Ghulam Abbas Ashraf; Saqib Bashir; Binglu Teng; Jureeporn Yuennan; Saqer S. Alotaibi; Muhammad Mushtaq (Journal of Water Process Engineering, 2025)

Occurrence, Distribution and Ecological Health Risk Assessment of Heavy Metals Through Consumption of Drinking Water in Urban, Industrial, and Mining Areas of Semi − Arid to Humid Subtropical Areas - Irfan Ullah; Muhammad Adnan; Javed Nawab; Irfan Safi; Sardar Khan (Journal of Geochemical Exploration, 2025)

How do media coverage and CEOs' ascribed ties help regulate corporate environmental responsibility in heavily polluting Chinese industries? - Huafei Wei; Lei Du; Muhammad Adnan Zahid Chudhery; Jun Chen (Journal of Cleaner Production, 2025)

Soil texture-driven modulation of poly-3-hydroxybutyrate (P3HB) biodegradation: Microbial shifts, and trade-offs between nutrient availability and lettuce growth - Martin Brtnicky; Adnan Mustafa; Jiri Holatko; Anna Gunina; Gabrijel Ondrasek; Muhammad Naveed; Tereza Hammerschmiedt; Eliska Kamenikova; Saud Alamri; Manzer H. Siddiqui; Antonin Kintl; Tivadar Baltazar; et al. (Environmental Research, 2025)

Global decline of aquatic and terrestrial insects driven by climate change and anthropogenic impacts: The interaction of multiple stressors and disruption of niche conservatism - Muhammad Farooq; Umair Khan; Muhammad Adnan; Waqar Younas; Nimra Bashir Qureshi; Qazi Muhammad Yasir; Qinghua Cai; Ming-Chih Chiu (Biological Conservation, 2025)

Microbial Synthesis of ZnO Nanoparticles: A Green Strategy for Mitigating Wastewater Stress in Wheat (Triticum aestivum) - Aneeza Ishfaq; Irfan Haidri; Usman Shafqat; Imran Khan; Hafiz Muhammad Rizwan; Muhammed Umair Hassan; Muhammad Irfan; Muhammad Adnan; Faisal Mahmood (Water, Air, & Soil Pollution, 2025)

Investigation of the genesis and intensification of simultaneous cyclones in the Arabian sea and Bay of Bengal in November 2020 - Abhishek Kumar; Arun Chakraborty; Mansour Almazroui; Muhammad Mubashar Dogar; Irfan Ur Rashid; Muhammad Adnan Abid; Moetasim Ashfaq (Theoretical and Applied Climatology, 2025)

Identification and analysis of abiotic stress-responsive bHLH gene family in Brassica oleracea - Muhammad Adnan Raza; Qin Wenjun; Song Jianghua (Horticulture, Environment, and Biotechnology, 2025)

Green and cost-effective photocatalytic degradation of murexide dye with acid catalyst - Zain Ul Abidin; Adnan Majeed; Muhammad Adnan Iqbal; Muhammad Kashif; Tabinda Fatima; Muhammad Yousif; Muhammad Arbaz; Syed Arslan Hussain; Muhammad Sajid (Clean Technologies and Environmental Policy, 2025)

Wild spices and their ecosystem service contributions in smallholder agroforestry systems of Aceh, Indonesia - Muhammad Jamil; Adnan Adnan; Heri Irawan; Zidni Ilman Navia; Adi Bejo Suwardi (Agroforestry Systems, 2025)

Selecting the best CMIP6 GCMs for application and downscaling studies over Pakistan, Nepal and Bangladesh - Shaukat Ali; Michelle Simões Reboita; Zulfiqar A. Bhutta; Muhammad Arif Goheer; Joao Gabriel Martins Ribeiro; Christie André de Souza; Glauber Willian Ferreira; Jai Das; Rida S. Kiani; Azfar Hussain; Fatima Saeed; Muhammad Adnan Abid; et al. (Acta Geophysica, 2025)

Phytoremediation potential of native medicinal plant species in mining degraded soil of Mohmand Northwest Pakistan - Irfan Ullah; Seemab Akhtar; Muhammad Adnan; Javed Nawab (Environmental Monitoring and Assessment, 2025)

A novel bio-based time-temperature dependent colorimetric indicator film incorporated with Amaranthus leaf extract for beef freshness tracking - Muhammad Shahar Yar; Isaiah Henry Ibeogu; Muhammad Adnan; Faiza Rehman; Abisikha Regmi; Meng Zhou; Muhammad Bilal; Zheng Liu; Hadiza Kabir Bako; Chunbao Li (Food Chemistry, 2025)

WITHDRAWN:The effects of soybean protein on lipid profile, bone health in post-menopausal women, comparing healthy vs. hyperlipidemic individuals and safety evaluation in rats. - Muhammad Adnan Manzoor; Adeela Yasmeen; Farhan Saeed; Shumaila Kiran (Food and Humanity, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Marine life as a source of anti-prostate cancer agents: an updated overview (2003–2023) - Amjad Hussain; Ammara Sohail; Muhammad Sajid Hamid Akash; Sarosh Iqbal; Kanwal Rehman; Muhammad Imran; Shoaib Khan; Muhammad Adnan Ayub; Daijie Wang; Dildar Ahmed; Mohammed Hadi Ali Al-Jumaili; Maria Bashir; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Evaluating the efficacy of nano-cyclosporine A in mice model of ulcerative colitis: a meta-analysis - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Nadia Shabnam; Adnan Haider; Shaista Aslam; Madiha Ghazanfar; Fakhar Ud-Din; Muhammad Irfan Siddique; Muhammad Naeem; Rida Fatima Saeed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Multiple integrated computational approach to analyse wound healing potential of Symplocos racemosa bark as Matrix metalloproteinase inhibitors - Hafiz Abdul Rafey; Adnan Amin; Samir Anis Ross; Mohamed El-Shazly; Muhammad Ammar Zahid; Shah Iram Niaz; Fakhar Ul Mahmood; Hammad Ullah (Natural Product Research, 2025)

An integrated comprehensive approach describing structural features and comparative petrophysical analysis between conventional and machine learning tools to characterize carbonate reservoir: A case study from Upper Indus Basin, Pakistan - Zohaib Naseer; Urooj Shakir; Muyyassar Hussain; Qazi Adnan Ahmad; Kamal Abdelrahman; Muhammad Fahad Mahmood; Mohammed S. Fnais; Muhsan Ehsan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Catharanthus roseus (L.) G. Don: A herb with the potential for curing breast cancer - Syeda Syesha Saman; Aqsa Hanif; Sawsan S. Al-Rawi; Ahmad H. Ibrahim; Muhammad Adnan Iqbal; Sabha Khalid; Adnan Majeed; Athar Mahmood; Farhan Ahmad (Next Research, 2025)

Probing the active kinematics in northwestern Himalayan foreland, Pakistan: Insights from seismicity and gravity data - Mohammad Tahir; Bilal Saif; Tahir Muhammad Iqbal; Raja Adnan Habib; Talat Iqbal; Muhammad Awais; Muhammad Ali Shah (Journal of Geodynamics, 2025)

Sorbitol induces sub-chronic nephrotoxicity via escalating JAK1/STAT3, oxidative stress and inflammation in Sprague Dawley rats - Fuad M. Alzahrani; Aqsa Bibi; Muhammad Faisal Hayat; Khalid J. Alzahrani; Khalaf F. Alsharif; Adnan Ali (Food and Chemical Toxicology, 2025)

Forecasting maximal and minimal air temperatures using explainable machine learning: Shapley additive explanation versus local interpretable model-agnostic explanations - Noureddine Daif; Fabio Di Nunno; Francesco Granata; Salah Difi; Ozgur Kisi; Salim Heddam; Sungwon Kim; Rana Muhammad Adnan; Mohammad Zounemat-Kermani (Stochastic Environmental Research and Risk Assessment, 2025)

Plant Growth Promoting Rhizobacteria Regulated Nutrient Uptake in Quinoa (Chenopodium Quinoa Wild) Under Nutrient-Deficient Conditions Through Solubilizing Insoluble Minerals - Ejaz Rafique; Muhammad Zahid Mumtaz; Lingling Li; Inam Ullah; Talha Ali Chohan; Muhammad Waqar Alam; Adnan Mustafa; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

Synthesis and Antibacterial Studies of Silver Loaded TiO2 Electrospun Nanofibers Against E. coli by Fluorescence Spectroscopy and Microscopy - Bisma Khanam; Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Muhammad Zakria; Taj Muhammad Khan; A. Rahman; Ahmad Adnan; Nida Ali Shan; Muhammad Raffi (Journal of Fluorescence, 2025)

Non-leguminous green manures improve labile phosphorus availability and crop yield in agroecosystems: A global meta-analysis - Adnan Anwar Khan; Imran Azeem; Jing Hui; Yupei Chen; Yuqi Yuan; Tahir Shah; Muhammad Adeel; Noman Shakoor; Rana Muhammad Ammar Asghar; Weidong Cao; Dabin Zhang; Yajun Gao (Soil and Tillage Research, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Ostrich oil evaluation; Parallel to food and pharmaceutical industries requirements: A review - Shehnshah Zafar; Adnan Amjad; Muhammad Tauseef Sultan; Muhammad Mueed Tanveer Malik (Food and Humanity, 2025)

Impact of End-capped Acceptor Modification in Anthanthrone-Based D-π-A Type Donor Materials for Organic and as Hole Transporting Materials for Perovskite Solar Cells - Nabeel Shahzad; Shahzad Ali Shahid Chatha; Riaz Hussain; Shahid Hussain; Javed Iqbal; Muhammad Adnan (Journal of Fluorescence, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Different fates between extracellular and intracellular antimicrobial resistome in full-scale activated sludge and membrane bioreactor processes - Mardalisa; Rongxuan Wang; Muhammad Adnan Sabar; Norihisa Matsuura; Hiroe Hara-Yamamura; Ryo Honda (Water Research, 2025)

Improved random vector functional link network with an enhanced remora optimization algorithm for predicting monthly streamflow - Rana Muhammad Adnan; Reham R. Mostafa; Mo Wang; Kulwinder Singh Parmar; Ozgur Kisi; Mohammad Zounemat-Kermani (Journal of Hydrology, 2025)

Enhancing BOD5 forecasting accuracy with the ANN-Enhanced Runge Kutta model - Rana Muhammad Adnan; Ahmed A. Ewees; Mo Wang; Ozgur Kisi; Salim Heddam; Kulwinder Singh Parmar; Mohammad Zounemat-Kermani (Journal of Environmental Chemical Engineering, 2025)

Superhydrophilic wettability porous materials from construction tooil/water separation applications - Muhammad Naseem; Mansoor Sultan; Mazhar ul Islam; Abdul Kareem; Nisar Ali; Ibrahim Khan; Shakeel Ahmad; Farooq nawaz; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Fuel, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Correction: Bol-miR168a is a key regulator of defense responses to Sclerotinia sclerotiorum in Brassica oleracea - Dandan Zha; Muhammad Adnan Raza; Xiaomeng Ye; Jianghua Song (Plant Cell Reports, 2025)

Mathematical study of infectious disease of pines caused by bark beetles - Takasar Hussain; Muhammad Ozair; Adnan Aslam; Maham Afaq; Muhammad Tanveer; Muhammad Awais; J. F. Gómez-Aguilar (Modeling Earth Systems and Environment, 2025)

Jasminum humile extract mitigates carrageenan-induced paw oedema in rats by modulating inflammatory and antioxidant signalling pathways - Mehreen Fatima; Lamya Ahmed Al-Keridis; Mohd Adnan; Nawaf Alshammari; Abdel Moneim Elhadi Sulieman; Muhammad Rashid Khan (Inflammopharmacology, 2025)

Tracking the tropical aquatic dragon: environmental DNA (eDNA) detection for monitoring the endangered Asian arowana, Scleropages formosus (Müller and Schlegel, 1840) - Norli Fauzani Mohd Abu Hassan Alshari; Muhammad Hanif Iryani Adnan; Danial Hariz Zainal Abidin; Siti Zafirah Ghazali; Min Pau Tan; Noor Adelyna Mohammed Akib; Sébastien Lavoué; Siti Azizah Mohd Nor (Hydrobiologia, 2025)

Highly efficient degradation of norfloxacin by using Co3O4-CeO2 as a heterogeneous catalyst through peroxymonosulfate activation: Characterization, catalytic performance and mechanism - Muhammad Rafiq; Raza Ullah; Adeel Ahmed; Xin Liu; Muhammad Usman; Qinghua Cao; Muhammad Adnan; Muhammad Fayaz; Waqas Haider; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2025)

Silent threats of lead-based paints in toys and households to children’s health and development - Muhammad Ubaid Ali; Muhammad Zeeshan Gulzar; Bisma Sattar; Sajeela Sehar; Qumber Abbas; Muhammad Adnan; Jingwei Sun; Zhuanxi Luo; Gongren Hu; Ruilian Yu; Ming Hung Wong (Journal of Hazardous Materials, 2025)

Quest for environmental management and sustainability: Evaluating the drivers of territorial and consumption-based carbon emissions in G-20 economies - Muhammad Adnan Bashir; Li Qing; Shahid Manzoor; Shahzad Khan Durrani; Lin Jingting; Nasir Sultan (Journal of Environmental Management, 2025)

Retraction notice to “Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure” [J. Environ. Manag. 356 (2024) 120673] - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Effects of relative microplastic–biochar sizes and biofilm formation on fragmental microplastic retention in biochar filters - Natrasa Changlor; Chutiporn Inchana; Muhammad Adnan Sabar; Bongkotrat Suyamud; Jenyuk Lohwacharin (Environmental Research, 2025)

Bol-miR168a is a key regulator of defense responses to Sclerotinia sclerotiorum in Brassica oleracea - Dandan Zha; Muhammad Adnan Raza; Xiaomeng Ye; Jianghua Song (Plant Cell Reports, 2025)

Multi-model assessment of climate change impacts on drought characteristics - Adnan Dehghani; Fatemehsadat Mortazavizadeh; Amin Dehghani; Muhammad Bin Rahmat; Hadi Galavi; David Bolonio; Jing Lin Ng; Vahid Rezaverdinejad; Majid Mirzaei (Natural Hazards, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

Chitosan Induced Modification in Morpho-Physiological, Biochemical and Yield Attributes of Pea (Pisum Sativum L.) Under Salt Stress - Sumreen Anjum; Qurat-ul Ain; Mubeen Sarwar; Muhammad Waqar Alam; Zain Mushtaq; Adnan Mukhtar; M. Irfan Ashraf; Abdulrahman Alasmari (Journal of Soil Science and Plant Nutrition, 2025)

Heavy metals pollution in riverine sediments: Distribution, source, and environmental implications - Kifayatullah Khan; Muhammad Younas; Muhammad Yaseen; Hassan Sher; Afsheen Maryam; Sobhy M. Ibrahim; Adnan Adnan; Ahmad Ali; Muhammad Fawad; Akhtar Zeb Khan; Nasrullah Khan; Izaz Ali Shah (Environmental Monitoring and Assessment, 2025)

Experimental study of local scour around a compound pile under steady current - Muhammad Adnan; Ming Zhao; Helen Wu; Vatsal Dhamelia (Ocean Engineering, 2025)

Addressing dye phytotoxicity and soil contamination: The dual action of chemically synthesized zinc nanoparticles in simultaneous adsorption and soil health improvement - Zainab Naseem; Muhammad Naveed; Saher Nawaz; Raafia Anam Saeed; Manzer H. Siddiqui; Adnan Mustafa; Avelino Núñez-Delgado (Journal of Environmental Management, 2025)

Carbon sinks associated with biological carbon pump in karst surface waters: Progress, challenges, and prospects - Mingyu Shao; Zaihua Liu; Sibo Zeng; Hailong Sun; Haibo He; Muhammad Adnan; Junyao Yan; Liangxing Shi; Yongqiang Han; Chaowei Lai; Yan Fang (Environmental Research, 2025)

Simultaneous alleviation of antimony toxicity in rice and in-Vitro bio-accessibility by using biochar and seaweed based fertilizer blend - Muhammad Umair Hassan; Huang Guoqin; Muhammad Nawaz; Adnan Noor Shah; Shujuan Li; Tahir Abbas Khan; Khalid Mashay Al-Anazi; Mehmood Ali Noor; Adnan Rasheed; Xu Huifang; Sezai Ercisli (Environmental Pollution, 2025)

Edge computing and transfer learning-based short-term load forecasting for residential and commercial buildings - Muhammad Sajid Iqbal; Muhammad Adnan (Energy and Buildings, 2025)

A comprehensive review on phytochemistry, pharmacology, preclinical, and clinical trials of Cydonia oblonga - Tuba; Muhammad Ajaz Hussain; Gulzar Muhammad; Muhammad Arshad Raza; Adnan Ashraf; Muhammad Tahir Haseeb; Muhammad Mushtaq; Zahid Shafiq (Phytochemistry Reviews, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The introduction of the SARS-CoV-2 BA.4 lineage into Pakistan - Zaira Rehman; Katherine Edington; Zunera Jamal; Angelika Kritz-Wilson; Gytis Dudas; Samuel Sims; Richard Myers; Babak Afrough; Leena Inamdar; Syed Adnan Haider; Aamer Ikram; Muhammad Salman; et al. (Archives of Virology, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Alleviation of cadmium stress and improved growth performance of periwinkle (Catharanthus roseus L.) by foliar application of zinc oxide nanoparticles - Muhammad Ahsan; Emanuele Radicetti; Roberto Mancinelli; Hayssam M. Ali; Adnan Younis; Mateen Sajid; Abdul Manan; Sajjad Ali; Mohammad Valipour; Hira Zulfiqar (South African Journal of Botany, 2025)

Food-derived phytochemicals from functional food (Allium sativum) as VEGF-R1 inhibitors: A novel approach for triple-negative breast cancer therapy - Abia Mahboob; Rashida Bashir; Ahmad Adnan; Muhammad Umer Khan; Umair Khurshid; Anjum Khursheed; Mhdia Elhadi Osman; Halima Mustafa Elagib; Nuha M.E. Agabna (Food Bioscience, 2025)

Progressive Approaches in Ni(II) Contaminated Water Treatment: A Review of Adsorbent Strategies - Adnan Ahmed; Aidi Huo; Muhammad Ibrahim (Water, Air, & Soil Pollution, 2025)

Probing the Complex Interaction of Makran Subduction Zone with Regional Tectonic Features: Insights from Gravity and Seismic Source Parameters - Raja Adnan Habib; Muhammad Tahir Iqbal; Mohammad Salam; Mohammad Tahir; Javed Iqbal; Talat Iqbal (Pure and Applied Geophysics, 2025)

Teratological abnormalities in hard ticks (Acari: Ixodidae) from Pakistan - Ejaz Akbar; Shafi Ullah; Mashal M. Almutairi; Iram Liaqat; Muhammad Adnan; Abdulaziz Alouffi; Tetsuya Tanaka; Abid Ali (Experimental and Applied Acarology, 2025)

Developed strategies of artificial intelligence in the prediction flow river flood using evolutionary optimized algorithms of ANN - Rana Muhammad Adnan Ikram; Mo Wang; Hossein Moayedi; Mohammad Hossein Gholizadeh; Atefeh Ahmadi Dehrashid; Quynh T. Thi (Environment, Development and Sustainability, 2024)

The role of selenium and biochar nanoparticles in alleviating cadmium stress in wheat (Triticum aestivum L.) examined via morphophysiological traits and organic acid exudation patterns - Mohammad K. Okla; Sahar Mumtaz; Sadia Javed; Muhammad Hamzah Saleem; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; Muhammad Adnan; Shafaqat Ali (South African Journal of Botany, 2024)

Assessing the combined impacts of microplastics and nickel oxide nanomaterials on soybean growth and nitrogen fixation potential - Imran Azeem; Quanlong Wang; Muhammad Adeel; Noman Shakoor; Muhammad Zain; Adnan Anwar khan; Yuanbo Li; Kamran Azeem; Muhammad Nadeem; Guikai Zhu; Rui Yukui (Journal of Hazardous Materials, 2024)

CFD modeling of CO2 capture in a non-isothermal circulating fluidized bed riser using K2CO3 solid sorbent - Amolwan Sornvichai; Muhammad Adnan; Nouman Ahmad; Ratchanon Piemjaiswang; Pornpote Piumsomboon; Benjapon Chalermsinsuwan (Journal of Environmental Chemical Engineering, 2024)

Drought Priming Enhanced Grain Yield of Wheat Against Salinity Stress - Ashutus Singha; Jahidul Karim; Asif Adnan Prince; Nargis Akter; khalada Akter Runa; Muhammad Naqib; A. K. Mohibul Islam; Setu Roy; Jouadul Hasan (Water Conservation Science and Engineering, 2024)

Diagnostic study on extreme precipitation over Karachi during August 2020 - Amna Bibi; Shahzada Adnan; Muhammad Latif; Azmat Hayat Khan; Anjum Nazir Zaighum; Kalim Ullah (Meteorology and Atmospheric Physics, 2024)

Enhanced cadmium immobilization in soil using Fe- and Zn-doped biochar: Mechanisms and safety implications for Cicer arietinum L - Uzma Muzaffar; Muhammad Naveed; Zainab Naseem; Iqra Abid; Kashif Zulfiqar Amir; Saud Alamri; Muhammad Siddique; Martin Brtnicky; Adnan Mustafa (Chemosphere, 2024)

Palliative potential of velutin against abamectin induced cardiac toxicity via regulating JAK1/STAT3, NF-κB, Nrf-2/Keap-1 signaling pathways: An insight from molecular docking - Mahmoud El Safadi; Qurat-ul-Ain Ahmad; Muhammad Majeebullah; Adnan Ali; Ahmed Al-Emam; Giorgio Antoniolli; Tawaf Ali Shah; Ahmad Mohammad Salamatullah (Pesticide Biochemistry and Physiology, 2024)

Enhanced activation of peroxymonosulfate by nanomagnetic CoFe2O4-CeO2/g-C3N4 composites as a heterogeneous catalyst for metronidazole degradation - Adeel Ahmed; Muhammad Usman; Muhammad Rafiq; Muhammad Adnan; Raza Ullah; Hailin Cong; Bing Yu (Journal of Water Process Engineering, 2024)

Stoichiometric and bacterial eco-physiological insights into microbial resource availability in karst regions affected by clipping-and-burning - Ansa Rebi; Guan Wang; Tao Yang; Jasper Kanomanyanga; Irsa Ejaz; Adnan Mustafa; Muhammad Rizwan; Jinxing Zhou (Journal of Environmental Management, 2024)

Reclamation alters evapotranspiration and its biophysical controls in a meadow grassland on the Mongolian Plateau - Xiaobing Dong; Gang Dong; Jingyan Chen; Tsegaye Gemechu Legesse; Shicheng Jiang; Muhammad Adnan Akram; Lu-Ping Qu; Lulu Wang; Jianming Deng; Changliang Shao (Journal of Environmental Management, 2024)

The importance of sharing: wild plant knowledge in three valleys of Northern Pakistan - Adnan Ali Shah; Abid Raza; Naji Sulaiman; Dipak Khadka; Abdul Majid; Muhammad Abdul Aziz; Arshad Mehmood Abbasi; Mushtaq Ahmad; Andrea Pieroni (Plant Biosystems, 2024)

Towards sustainable manufacturing: unpacking green practices’ impact on environmental performance in Pakistan - Muhammad Bilal; Zhao Xicang; Wu Jiying; Muhammad Umair Wattoo; Muhammad Adnan (Environment, Development and Sustainability, 2024)

Income inequality-renewable energy demand nexus in emerging Asian economies: does asymmetry matter? - Yannan Gao; Danish Ahmed; Muhammad Hafeez; Qaisar Ali; Yawar Abbas; Adnan Maqbool (Environmental Science and Pollution Research, 2024)

Multifaceted roles of zinc nanoparticles in alleviating heavy metal toxicity in plants: a comprehensive review and future perspectives - Muhammad Umair Hassan; Huang Guoqin; Naeem Ahmad; Tahir Abbas Khan; Muhammad Nawaz; Adnan Noor Shah; Adnan Rasheed; Tahani A. Y. Asseri; Sezai Ercisli (Environmental Science and Pollution Research, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Experimental investigation of the wake of tandem cylinders using pivoted flapping mechanism for piezoelectric flag - Muhammad Mahad Shah; Rizwan Mahmood; Usman Latif; Emad Uddin; Adnan Munir; Ming Zhao; Hafiz Hamza Riaz (Ocean Engineering, 2024)

Corrigendum to ‘Unpacking the environmental quality through the effects of natural resources, renewable energy consumption, banking development and industrial value addition: An empirical evidence from BRICS countries’ [J. Environ. Manage. 367, September 2024, 122058] - Muhammad Adnan Bashir; Li Qing; Raf Dewil; Zhang Xi; Ummara Razi; Lin Jingting (Journal of Environmental Management, 2024)

Photocatalytic hydrogen peroxide production: Advances, mechanistic insights, and emerging challenges - Shahid Khan; Muhammad Adnan Qaiser; Waqar Ahmad Qureshi; Syed Najeeb-uz-Zaman Haider; Xiaohui Yu; Weikang Wang; Qinqin Liu (Journal of Environmental Chemical Engineering, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Perusing sustainable development through education: evidence from Malaysia, Indonesia and Pakistan - Farah Khan; Muhammad Adnan Khan; Haseeb Ur Rahman (Environment, Development and Sustainability, 2024)

High-resolution landslide mapping and susceptibility assessment: Landslide temporal variations and vegetation recovery - Muhammad Zeeshan Ali; Kejie Chen; Muhammad Shafique; Muhammad Adnan; Zhiwen Zheng; Wei Zhang; Zhanhui Qing (Advances in Space Research, 2024)

Triethylammonium Salts of Dicoumarol: Synthesis, Characterization, Human Antiglioblastoma, Antimicrobial and Antioxidant Studies - Sadia Rehman; Muhammad Ikram; Afzal Khan; Adnan Khan; Farzia; Rizwan Khan; Mutasem Omar Sinnokrot; Vinay K. Puduvalli; Ayub Jadoon (Cell Biochemistry and Biophysics, 2024)

Design and Evaluation of Inorganic/Organic Hybrid Bio-composite for Site-Specific Oral Delivery of Darifenacin - Wafa Ishaq; Attia Afzal; Muhammad Farooq; Muhammad Sarfraz; Sherjeel Adnan; Hammad Ahmed; Muhammad Waqas; Zainab Safdar (AAPS PharmSciTech, 2024)
Benign hyperplasia (BHP) is a common disorder that affects men over the age of 60 years. Transurethral resection of the prostate (TURP) is the gold standard for operative treatment, but a range of drugs are also available to improve quality of life and to reduce BHP-associated urinary tract infections and complications. Darifenacin, an anti-muscarinic agent, has been found effective for relieving symptoms of overactive bladder associated with BHP, but the drug has poor solubility and bioavailability, which are major challenges in product development. An inorganic/organic bio-composite with gastric pH-resistant property was synthesized for the targeted oral delivery of Darifenacin to the lower gastrointestinal tract (GIT). This development was accomplished through co-precipitation of calcium carbonate in quince seed-based mucilage. The FTIR, XRD, DSC, and TGA results showed good drug-polymer compatibility, and the SEM images showed calcite formation in the quince hydrogel system. After 72 h, the drug release of 34% and 75% were observed in acidic (0.1N HCl) and 6.8 pH phosphate buffer, respectively. A restricted/less drug was permeated through gastric membrane (21.8%) as compared to permeation through intestinal membrane (65%.) The developed composite showed significant reduction in testosterone-induced prostatic hyperplasia (2.39 ± 0.12***) as compared to untreated diseased animal group. No sign of organ toxicity was observed against all the developed composites. In this study, we developed an inorganic–organic composite system that is highly biocompatible and effective for targeting the lower GIT, thereby avoiding the first-pass metabolism of darifenacin. Graphical Abstract

Carbon based nanocomposites, surface functionalization as a promising material for VOCs (volatile organic compounds) treatment - Farooq Nawaz; Muhammad Ali; Shakeel Ahmad; Yang Yong; Suhaib Rahman; Muhammad Naseem; Sadam Hussain; Abdul Razzaq; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Chemosphere, 2024)

Unpacking the environmental quality through the effects of natural resources, renewable energy consumption, banking development and industrial value addition: An empirical evidence from BRICS countries - Muhammad Adnan Bashir; Li Qing; Zhang Xi; Ummara Razi; Lin Jingting (Journal of Environmental Management, 2024)

Effect of alfalfa-grass mixed culture and inoculation with Azotobacter and Rhizobium on soil biological properties and nutrient transformation activities - Jiri Holatko; Martin Brtnicky; Antonin Kintl; Tivadar Baltazar; Ondrej Malicek; Adnan Mustafa; Jiri Skladanka; Jiri Kucerik; Saud Alamri; Jan Lochman; Pavel Horky; Daniela Knotova; et al. (European Journal of Soil Biology, 2024)

Characterization and Induction of Biochar Induced Capsicum annumm Defense Against Bacterial Wilt - Muhammad Taqqi Abbas; Tehmina Anjum; Waheed Anwar; Muhammad Khurshid; Adnan Akhter (Journal of Soil Science and Plant Nutrition, 2024)

Predictability of the early summer surface air temperature over Western South Asia - Irfan Ur Rashid; Muhammad Adnan Abid; Marisol Osman; Fred Kucharski; Moetasim Ashfaq; Antje Weisheimer; Mansour Almazroui; José Abraham Torres-Alavez; Muhammad Afzaal (Climate Dynamics, 2024)
Variability of the Surface Air Temperature (SAT) over the Western South Asia (WSA) region leads to frequent heatwaves during the early summer (May-June) season. The present study uses the European Centre for Medium-Range Weather Forecast’s fifth-generation seasonal prediction system, SEAS5, from 1981 to 2022 based on April initial conditions (1-month lead) to assess the SAT predictability during early summer season. The goal is to evaluate the SEAS5’s ability to predict the El Niño-Southern Oscillation (ENSO) related interannual variability and predictability of the SAT over WSA, which is mediated through upper-level (200-hPa) geopotential height anomalies. This teleconnection leads to anomalously warm surface conditions over the region during the negative ENSO phase, as observed in the reanalysis and SEAS5. We evaluate SEAS5 prediction skill against two observations and three reanalyses datasets. The SEAS5 SAT prediction skill is higher with high spatial resolution observations and reanalysis datasets compared to the ones with low-resolution. Overall, SEAS5 shows reasonable skill in predicting SAT and its variability over the WSA region. Moreover, the predictability of SAT during La Niña is comparable to El Niño years over the WSA region.

Artificial neural network modeling for the prediction, estimation, and treatment of diverse wastewaters: A comprehensive review and future perspective - Muhammad Ibrahim; Adnan Haider; Jun Wei Lim; Bandita Mainali; Muhammad Aslam; Mathava Kumar; Muhammad Kashif Shahid (Chemosphere, 2024)

Analyze the effect of energy efficiency, natural resources, and the digital economy on ecological footprint in OCED countries: The mediating role of renewable energy - Dengfeng Zhao; Jingting Lin; Muhammad Adnan Bashir (Resources Policy, 2024)

Resources policy from extraction to innovation: The interplay of minerals, geothermal energy, technological advancements, and ecological footprint in high-ecological footprint economies - Muhammad Adnan Bashir; Li Qing; Qasim Raza Syed; Anna Barwińska-Małajowicz; Shabir Mohsin Hashmi (Resources Policy, 2024)

Development of energy efficient flower-shaped defective TiO2 materials for wastewater remediation of agro-industries and oil refineries - Rab Nawaz; Marlia Mohd Hanafiah; Sajjad Haider; Muzammil Anjum; Mujahid Ali; Rawaiz Khan; Sammia Khurshid; Shafi Ullah; Muhammad Aqif; Adnan Haider; Zaher Abdel Baki (Process Safety and Environmental Protection, 2024)

A novel computational methodology to design solar radiation absorbing glass - Faraan Fareed; Uzma Habib; Hafiz Ali Haider Sehole; Salma Sherbaz; Muhammad Bilal Khan Niazi; Adnan Maqsood (Energy and Buildings, 2024)

Drought variability in Pakistan: Navigating historical patterns in a changing climate with global teleconnections - Muhammad Latif; Hira Shireen; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi (Theoretical and Applied Climatology, 2024)

Designing and synthesis of perovskite nanocrystals: a promising wide-spectrum solar light–responsive photocatalyst and lead ion sensor - Nisar Ali; Shakeel Ahmad; Arif Nawaz; Manzoor Khan; Aman Ullah; Muhammad Idrees; Adnan Khan; Wilayat Khan (Environmental Science and Pollution Research, 2024)

Retraction Note: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Nano-based remediation strategies for micro and nanoplastic pollution - Nayab Batool Rizvi; Adnan Sarwar; Saba Waheed; Zeenat Fatima Iqbal; Muhammad Imran; Ayesha Javaid; Tak H. Kim; Muhammad Shahzeb Khan (Journal of Contaminant Hydrology, 2024)

Distribution and bioaccumulation of trace elements in two Cyprinidae fish species in the Indus river, Pakistan, including the impact of hydraulic structure on macroinvertebrates' biodiversity - Muhammad Waseem Boota; Shan-e-hyder Soomro; Haoming Xia; Yaochen Qin; Mian Adnan Kakakhel; Chaode Yan; Luo Weiran; Jikun Xu (Environmental Research, 2024)

Analyzing the Role of Changing Climate on the Variability of Intensity-Duration-Frequency Curve Using Wavelet Analysis - Syed Adnan Shah; Hamza Farooq Gabriel; Muhammad Waqar Saleem; Nuaman Ejaz; Songhao Shang; Deqiang Mao; Khalil Ur Rahman (Water Resources Management, 2024)

Response of cotton mealybug, Phenacoccus Solenopsis Tinsley (Sternorrhyncha: Pseudococcidae) to predators, neem oil, and synthetic insecticide under semi-field and field conditions - Muhammad Mamoon-ur-Rashid; Khalid Abdullah; Habib Ali; Muhammad Tariq; Adnan Noor Shah; Shahbaz Ali (International Journal of Tropical Insect Science, 2024)

Which bioenergy with carbon capture and storage (BECCS) pathways can provide net-negative emissions? - Muhammad Adnan Hayat; Khalid Alhadhrami; Amro M. Elshurafa (International Journal of Greenhouse Gas Control, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Solar Light Assisted Metal Selenide-Chitosan Nanoparticles from Structure Tailoring to Photocatalytic Mineralization of Selected Industrial Dyes - Javeed Azam; Muhammad Farhan; Adnan Khan; Tariq Aziz; Nauman Ali; Hamayun Khan; Sumeet Malik; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Bio-upcycling of plastic waste: a sustainable innovative approach for circular economy - Sadia Mehmood Satti; Muzna Hashmi; Mishal Subhan; Muhammad Adnan Shereen; Adham Fayad; Asim Abbasi; Aamer Ali Shah; Hayssam M. Ali (Water, Air, & Soil Pollution, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Soil Organic Carbon and Nitrogen Mineralization Potential of Manures Regulated by Soil Microbial Activities in Contrasting Soil Textures - Waqar Ahmed; Muhammad Nadeem Ashraf; Muhammad Sanaullah; Muhammad Aamir Maqsood; Muhammad Ahmed Waqas; Shafeeq Ur Rahman; Saddam Hussain; Hammad Raza Ahmad; Adnan Mustafa; Xu Minggang (Journal of Soil Science and Plant Nutrition, 2024)

Morpho-Physiological and Enzymatic Responses of Zinnia (Zinnia elegans L.) to Different Metal Hoarded Wastewaters - Muhammad Ahsan; Adnan Younis; Muhammad Raheel; Imran Khalid; Hafiz Tassawar Abbas; Waqas Ashraf; Adil Mihoub; Emanuele Radicetti; Muhammad Farhan Saeed; Sajjad Ali; Mohammad Valipour; Aftab Jamal (Journal of Soil Science and Plant Nutrition, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

Integrating FinTech with Industry 4.0 for sustainable mineral resource management: Exploring the interplay of technology, regulation, and economic dynamics - Imran Khan; Inayat Khan; Rana Muhammad Adnan Ikram; Mohammad Ajmal Ali (Resources Policy, 2024)

Unraveling the impact of wildfires on permafrost ecosystems: Vulnerability, implications, and management strategies - Ansa Rebi; Guan Wang; Muhammad Irfan; Azfar Hussain; Adnan Mustafa; Trevan Flynn; Irsa Ejaz; Taqi Raza; Parsa Mushtaq; Muhammad Rizwan; Jinxing Zhou (Journal of Environmental Management, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

SPEEDY-NEMO: performance and applications of a fully-coupled intermediate-complexity climate model - Paolo Ruggieri; Muhammad Adnan Abid; Javier García-Serrano; Carlo Grancini; Fred Kucharski; Salvatore Pascale; Danila Volpi (Climate Dynamics, 2024)
A fully-coupled general circulation model of intermediate complexity is documented. The study presents an overview of the model climatology and variability, with particular attention to the phenomenology of processes that are relevant for the predictability of the climate system on seasonal-to-decadal time-scales. It is shown that the model can realistically simulate the general circulation of the atmosphere and the ocean, as well as the major modes of climate variability on the examined time-scales: e.g. El Niño-Southern Oscillation, North Atlantic Oscillation, Tropical Atlantic Variability, Pacific Decadal Variability, Atlantic Multi-decadal Variability. Potential applications of the model are discussed, with emphasis on the possibility of generating sets of low-cost large-ensemble retrospective forecasts. We argue that the presented model is suitable to be employed in traditional and innovative model experiments that can play a significant role in future developments of seasonal-to-decadal climate prediction.

Genomic characterization of human respiratory syncytial virus circulating in Islamabad, Pakistan, during an outbreak in 2022-2023 - Syed Adnan Haider; Zunera Jamal; Faheem Tahir; Muhammad Salman; Massab Umair (Archives of Virology, 2024)

Elucidating the Mechanism of Copper-Induced Photoluminescence Quenching in 2-Phenylbenzimidazole-5-Sulfonic Acid - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Poshmal Sumreen; Mamoona Tabassum; Shoaib Ashiq; Sheikh Aadil Abbas; Raheel Akram; Azhar Iqbal (Journal of Fluorescence, 2024)

Exploring Bacillus mycoides PM35 efficacy in enhancing rice (Oryza sativa L.) response to different types of microplastics through gene regulation and cellular fractionation - Dalal Nasser Binjawhar; Rana M. Alshegaihi; Aishah Alatawi; Muneefah Abdullah Alenezi; Abida Parveen; Muhammad Adnan; Baber Ali; Khalid Ali Khan; Shah Fahad; Eman Fayad (Environmental Science and Pollution Research, 2024)

Divergent responses of phosphorus solubilizing bacteria with P-laden biochar for enhancing nutrient recovery, growth, and yield of canola (Brassica napus L.) - Muhammad Farhan Qadir; Muhammad Naveed; Khuram Shehzad Khan; Tooba Mumtaz; Taqi Raza; Waqas Mohy-Ud-Din; Adnan Mustafa (Chemosphere, 2024)

RETRACTED: Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Novel polyamide-hydrazide based reverse osmosis membrane with enhanced antifouling properties - Zhongyang Wang; Muhammad Adnan Akram; Shanshan Zhang; Jingwei Gong; Lihua Zhao; Zhiyu Liu; Q. Jason Niu (Desalination, 2024)

Brown macro-seaweeds derived agro-biostimulant for Zea mays farming in saline conditions: Growth enhancement and optimum biochemical and ion feedback - Sadaf Gul; Muhammad Farrakh Nawaz; Muhammad Talha Bin Yousaf; Muhammad Haroon U Rashid; Muhammad Yousuf Adnan; Shamama Tausif; Arooj Javed; Zainul Abideen; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Identification of a novel marker and its associated laccase gene for regulating ear length in tropical and subtropical maize lines - Yaqi Bi; Fuyan Jiang; Yudong Zhang; Ziwei Li; Tianhui Kuang; Ranjan K. Shaw; Muhammad Adnan; Kunzhi Li; Xingming Fan (Theoretical and Applied Genetics, 2024)
Key message This study revealed the identification of a novel gene, Zm00001d042906 , that regulates maize ear length by modulating lignin synthesis and reported a molecular marker for selecting maize lines with elongated ears. Abstract Maize ear length has garnered considerable attention due to its high correlation with yield. In this study, six maize inbred lines of significant importance in maize breeding were used as parents. The temperate maize inbred line Ye107, characterized by a short ear, was crossed with five tropical or subtropical inbred lines featuring longer ears, creating a multi-parent population displaying significant variations in ear length. Through genome-wide association studies and mutation analysis, the A/G variation at SNP_183573532 on chromosome 3 was identified as an effective site for discriminating long-ear maize. Furthermore, the associated gene Zm00001d042906 was found to correlate with maize ear length. Zm00001d042906 was functionally annotated as a laccase ( Lac4 ), which showed activity and influenced lignin synthesis in the midsection cells of the cob, thereby regulating maize ear length. This study further reports a novel molecular marker and a new gene that can assist maize breeding programs in selecting varieties with elongated ears.

Spatiotemporal analyses of temperature and equivalent temperature and their relationship with crop health across Pakistan’s cropland - Muhammad Latif; Momel Zoon; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi; Rashed Mahmood; Muhammad Umar (Theoretical and Applied Climatology, 2024)

Genome-wide identification and in-silico expression analysis of CCO gene family in sunflower (Helianthus annuus) against abiotic stress - Adnan Sami; Muhammad Zeeshan Haider; Muhammad Shafiq; Saleh Sadiq; Farooq Ahmad (Plant Molecular Biology, 2024)
Carotenoid cleavage oxygenases (CCOs) enzymes play an important role in plant growth and development by producing a wide array of apocarotenoids and their derivatives. These compounds are vital for colouring flowers and fruits and synthesizing plant hormones such as abscisic acid and strigolactones. Despite their importance, the gene family responsible for CCO enzymes in sunflowers has not been identified. In this study, we identify the CCO genes of the sunflower plant to fill this knowledge gap. Phylogenetic and synteny analysis indicated that the Helianthus annuus CCO (HaCCO) genes were conserved in different plant species and they could be divided into three subgroups based on their conserved domains. Analysis using MEME tool and multiple sequence alignment identified conserved motifs in the HaCCO gene sequence. Cis -regulatory elements (CREs) analysis of the HaCCO genes indicated the presence of various responsive elements related to plant hormones, development, and responses to both biotic and abiotic stresses. This implies that these genes may respond to plant hormones, developmental cues, and drought stress, offering potential applications in the development of more resistant crops. Genes belonging to the 9-cis-epoxy carotenoid dioxygenases (NCED) subgroups predominantly exhibited chloroplast localization, whereas the genes found in other groups are primarily localized in the cytoplasm. These 21 identified HaCCOs were regulated by 60 miRNAs, indicating the crucial role of microRNAs in gene regulation in sunflowers. Gene expression analysis under drought stress revealed significant up-regulation of HaNCED16 and HaNCED19 , genes that are pivotal in ABA hormone biosynthesis. During organ-specific gene expression analysis, HaCCD12 and HaCCD20 genes exhibit higher activity in leaves, indicating a potential role in leaf pigmentation. This study provides a foundation for future research on the regulation and functions of the CCO gene family in sunflower and beyond. There is potential for developing molecular markers that could be employed in breeding programs to create new sunflower lines resistant to biotic and abiotic stresses.

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

The coincidence of climate extremes with sensitive crop growth phases: Projected impact on sustainable crop water use and crop yield in the IGB river basins - Qurat-ul-Ain Ahmad; Eddy Moors; Ilyas Masih; Nuzba Shaheen; Hester Biemans; Muhammad Adnan (Science of The Total Environment, 2024)

Mineral resource Optimization: The Nexus of sustainability, digital transformation, and green finance in OECD economies - Min Zhong; Muhammad Umar; Nawazish Mirza; Adnan Safi (Resources Policy, 2024)

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

Substation of vermicompost mitigates Cd toxicity, improves rice yields and restores bacterial community in a Cd-contaminated soil in Southern China - Anas Iqbal; Jiang Ligeng; Zhaowen Mo; Muhammad Adnan; Rattan Lal; Maid Zaman; Sayed Usman; Tian Hua; Muhammad Imran; Sheng-Gang Pan; Jian-Ying Qi; Meiyang Duan; et al. (Journal of Hazardous Materials, 2024)

Coarse-graining dense discrete phase model for modeling particle dynamics in a 3D tapered fluidized bed coater: Analysis of different drag models - Muhammad Adnan; Nouman Ahmad; Pornpote Piumsomboon; Benjapon Chalermsinsuwan (Journal of Food Engineering, 2024)

A fast and efficient phenotyping method to estimate sugarcane stalk bending properties using near-infrared spectroscopy - Fumin Ma; Maoyao Wang; Ning Yan; Muhammad Adnan; Fuhong Jiang; Qian Hu; Guanyong He; Yinjuan Shen; Yan Wan; Yixian Yang; Shaojing Liang; Xiaoru Chen; et al. (European Journal of Agronomy, 2024)

Ethnobotanical, ecological and health risk assessment of some selected wild medicinal plants collected along mafic and Ultra Mafic rocks of Northwest Pakistan - Irfan Ullah; Muhammad Adnan; Javed Nawab; Sardar Khan (Environmental Monitoring and Assessment, 2024)

Investigating the unparalleled effects of economic growth and high-quality economic development on energy insecurity in China: A provincial perspective - Jabbar Ul-Haq; Hubert Visas; Qazi Muhammad Adnan Hye; Raja Rehan; Sana Khanum (Environmental Science and Pollution Research, 2024)

Impacts and mechanism of coal fly ash on kitchen waste composting performance: The perspective of microbial community - Tahir Muhammad; Cuiling Jiang; Yunkai Li; Irum Manan; Changjian Ma; Hui Geng; Iza Fatima; Muhammad Adnan (Chemosphere, 2024)

Insight into microplastics in the aquatic ecosystem: Properties, sources, threats and mitigation strategies - Nisar Ali; Muhammad Hamid Khan; Muhammad Ali; Sidra; Shakeel Ahmad; Adnan Khan; Ghulam Nabi; Farman Ali; Mohamed Bououdina; George Z. Kyzas (Science of The Total Environment, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Melatonin supplementation alleviates drought stress in peach (Prunus persica) seedlings by improving photosynthesis, root morphological traits, and antioxidant defense system - Shahid Iqbal; Faisal Hayat; Mujahid Hussain; Naveed Mushtaq; Muneer Rehman; Alaiha Asif; Ummara Khan; Muhammad Adnan Shahid (Acta Physiologiae Plantarum, 2024)

A winning formula: sustainable control of three stored-product insects through paired combinations of entomopathogenic fungus, diatomaceous earth, and lambda-cyhalothrin - Waqas Wakil; Nickolas G. Kavallieratos; Nikoleta Eleftheriadou; Syed Adnan Haider; Mirza Abdul Qayyum; Muhammad Tahir; Khawaja G. Rasool; Mureed Husain; Abdulrahman S. Aldawood (Environmental Science and Pollution Research, 2024)
This research aimed to assess the effectiveness of Metarhizium robertsii , diatomaceous earth (Protect-It), and lambda-cyhalothrin, for the long-term protection of stored wheat against three destructive grain insect pests, Rhyzopertha dominica , Tribolium castaneum , and Trogoderma granarium . Different treatments were applied, both alone and in paired combinations in laboratory and persistence trials. Single treatments exhibited significantly lower mortality rates in comparison to the paired treatments for all tested insect species. Among the single treatments, lambda-cyhalothrin (Lamb) resulted in significantly higher mortality rates in laboratory trials, followed by diatomaceous earth (DE) and M. robertsii (Mr), with insignificant differences between Mr and DE. Evidently, DE exhibited the highest persistence after 120 days of storage for all insect species and initial exposures, although variations in mortality rates among treatments were mostly insignificant. Overall, the most effective treatment in terms of mortality in laboratory, and persistence trials, and progeny production was DE + Lamb, followed by Mr + Lamb, and Mr + DE for all tested insect species. In general, the most susceptible insect species was R. dominica , followed by T. castaneum and T. granarium . This research highlights the effectiveness of M. robertsii , DE, and lambda-cyhalothrin in providing prolonged protection of stored wheat against all the examined grain insect species.

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Matrix scenario-based urban flooding damage prediction via convolutional neural network - Haojun Yuan; Mo Wang; Jianjun Li; Dongqing Zhang; Rana Muhammad Adnan Ikram; Jin Su; Shiqi Zhou; Yuankai Wang; Qifei Zhang (Journal of Environmental Management, 2024)

Predicting steady-state biogas production from waste using advanced machine learning-metaheuristic approaches - Yesen Sun; Hong-liang Dai; Hossein Moayedi; Binh Nguyen Le; Rana Muhammad Adnan (Fuel, 2024)

Phytotoxicity of radionuclides: A review of sources, impacts and remediation strategies - Shahzaib Ali; Sadia Babar Baloch; Jaroslav Bernas; Petr Konvalina; Eze Festus Onyebuchi; Muhammad Naveed; Hassan Ali; Zameer Hussain Jamali; Mohammad Tahsin Karimi Nezhad; Adnan Mustafa (Environmental Research, 2024)

Improved prediction of monthly streamflow in a mountainous region by Metaheuristic-Enhanced deep learning and machine learning models using hydroclimatic data - Rana Muhammad Adnan; Amin Mirboluki; Mojtaba Mehraein; Anurag Malik; Salim Heddam; Ozgur Kisi (Theoretical and Applied Climatology, 2024)

The application of multi-attribute decision making methods in integrated watershed management - Rana Muhammad Adnan Ikram; Sarita Gajbhiye Meshram; Mohd Abul Hasan; Xinyi Cao; Ehsan Alvandi; Chandrashekhar Meshram; Saiful Islam (Stochastic Environmental Research and Risk Assessment, 2024)

Retraction Note: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Spatiotemporal variability of precipitation concentration in Pakistan - Muhammad Zaman; Muhammad Adnan Shahid; Ijaz Ahmad; Yan‐Jun Shen; Muhammad Usman; Muhammad Imran Khan; Muhammad Saifullah (International Journal of Climatology, 2023)
Precipitation is a meteorological variable that plays a vital role in determining water resources and managing water risks. The intensity and frequency of precipitation extremes have increased in recent years; however, the changes in precipitation regimes across Pakistan remain unclear. This study analysed spatial and temporal changes in the precipitation concentration index (PCI) and concentration index (CI) from 100 meteorological stations across Pakistan from 1981 to 2017. Using innovative trend analysis (ITA) and Pettitt's test, we detected trends and change points in the annual and wet season PCI and CI. Additionally, we examined the relationship between PCI/CI values and latitude and altitude. The results revealed that the CI and PCI ranged between 0.48–0.78 and 10–55, respectively, with higher values being more prevalent in the dry and hot zones of the country. The study established a linear relationship between PCI/CI values, latitude and altitude, with higher values at lower altitudes and a decrease in values from south to north. Most stations presented a significant positive ITA trend for PCI and CI from 1981 to 2017, with a change between 1985 and 1995, indicating an overall increase in heavy precipitation events in the area. These findings are crucial for disaster preparedness, water resource planning, the mitigation of drought and flood risks, and conservation efforts.

Corporate social responsibility—an antidote for sustainable business performance: interconnecting role of digital technologies, employee eco-behavior, and tax avoidance - Syed Abdul Rehman Khan; Adnan Ahmed Sheikh; Muhammad Sohail Tahir (Environmental Science and Pollution Research, 2023)

Can sustainable resource management overcome geopolitical risk? - Adnan Safi; Muhammad Haseeb; Madeeha Islam; Muhammad Umar (Resources Policy, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Different Rotation and Double Straw Returning Significantly Increase Liable Organic Carbon Content and Yield of Double Cropping Paddy Field in Southern China - Zhiqiang Wang; Haiying Tang; Guoqin Huang; Jianqun Miao; Ying Liu; Adnan Noor Shah; Muhammad Nawaz; Muhammad Ahsin Ayub; Muhammad Umair Hassan (International Journal of Plant Production, 2023)

Probabilistic modelling of interarrival time of drought for different operational drought indices used in Pakistan - Muhammad Mohsin; Shahzada Adnan (International Journal of Climatology, 2023)
Adverse climate changes in Pakistan undermine the water resources and give rise to transient and permanent droughts in different parts of the country. The occurrence of drought cannot be prevented, but its detrimental impacts can be brought down by proper pre‐drought planning. Effective planning owes to using scientific and probabilistic approaches. In this paper, the interarrival time of drought for seven operational drought indices in Pakistan is modelled by using the modified distribution of convolution derived from the Bivariate Affine Linear Exponential (BALE) distribution. A new stochastic variable, interarrival time of drought, is generated from the data of drought indices from 1951 to 2016 used in Pakistan by applying the theory of runs. The proposed model identifies Palmer drought severity index (PDSI) and Reconnaissance drought index (RDI) as the most appropriate meteorological indices for the under‐study country. The quantiles of the model are computed that provide information about the interarrival time of drought and help to anticipate this phenomenon. In addition, return periods for all the seven indices are calculated to report the frequency and duration of drought over a certain period. Finally, some recommendations for the National Drought Monitoring Centre (NDMC) and Pakistan Council of Research in Water Resources (PCRWR) are stated for better future planning to avoid the adverse impacts of drought.

Development of the artificial neural network’s swarm-based approaches predicting East Azerbaijan landslide susceptibility mapping - Yesen Sun; Hong-liang Dai; Lei Xu; Abed Asaditaleshi; Atefeh Ahmadi Dehrashid; Rana Muhammad Adnan Ikram; Hossein Moayedi; Hossein Ahmadi Dehrashid; Quynh T. Thi (Environment, Development and Sustainability, 2023)

Impacts of nutritive and bioactive compounds on cancer development and therapy - Sabira Sultana; Abdelhakim Bouyahya; Maksim Rebezov; Mohammad Ali Shariati; Abdelaali Balahbib; Aya Khouchlaa; Ouadie Mohamed El Yaagoubi; Adnan Khaliq; Nasreddine El Omari; Saad Bakrim; Gokhan Zengin; Muhammad Akram; et al. (Critical Reviews in Food Science and Nutrition, 2023)

RETRACTED: Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Probing the Förster Resonance Energy Transfer Dynamics in Colloidal Donor-Acceptor Quantum Dots Assemblies - Muhammad Adnan Khalid; Muhammad Mubeen; Maria Mukhtar; Zumaira Siddique; Poshmal Sumreen; Firdevs Aydın; Demet Asil; Azhar Iqbal (Journal of Fluorescence, 2023)

Moisture sources for precipitation variability over the Arabian Peninsula - Matthew F. Horan; Fulden Batibeniz; Fred Kucharski; Mansour Almazroui; Muhammad Adnan Abid; Joshua S. Fu; Moetasim Ashfaq (Climate Dynamics, 2023)
We apply the Lagrangian-based moisture back trajectory method to two reanalysis datasets to determine the moisture sources for wet season precipitation over the Arabian Peninsula, defined as land on the Asian continent to the south of the Turkish border and west of Iran. To accomplish this, we make use of the evaporative source region between 65°W–120°E and 30°S–60°N, which is divided into twelve sub-regions. Our comparison of reanalyses and multiple observations allows us to validate datasets and highlight broad-scale similarities in characteristics, notwithstanding some inconsistencies in the southwest AP. The results indicate north-to-south spatiotemporal heterogeneity in the characteristics of dominant moisture sources. In the north, moisture for precipitation is mainly sourced from midlatitude land and water bodies, such as the Mediterranean and Caspian Seas. Areas further south are dependent on moisture transport from the Western Indian Ocean and parts of the African continent. The El Niño-Southern Oscillation (ENSO) exhibits an overall positive but sub-seasonally varying influence on the precipitation variability over the region, with noticeable moisture anomalies from all major source regions. A significant drying trend exists over parts of the Peninsula, which both reanalyses partially attribute to anomalies in the moisture advection from the Congo Basin and South Atlantic Ocean. However, considerable uncertainty in evaporation trends over the terrestrial evaporative sources in observations warrants additional modeling studies to further our understanding of key processes contributing to the negative trends.

Variations of b-value and the ω-upper bound magnitude of GIII distribution of the Pamir–Hindu Kush region - Khaista Rehman; Wajid Ali; Muhammad Shafique; Aamir Ali; Adnan Barkat; Waqas Ahmed; Muhammad Waqar Azeem (Arabian Journal of Geosciences, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Examining the role of natural resource rent, environmental regulations, and environmental taxes in sustainable development: Evidence from G-7 economies - Nada Khaddage-Soboh; Adnan Safi; Muhammad Faisal Rasheed; Amir Hasnaoui (Resources Policy, 2023)

Efficient removal of hexavalent chromium Cr (VI) using magnesium-iron layered double hydroxide supported on orange peel (Mg-Fe LDH@OPP): A synthetic experimental and mechanism studies - Waleed Usmani; Muhammad Ali Inam; Rashid Iftikhar; Iqra Irfan; Rabia Adnan; Muhammad Bilal Khan Niazi; Rizwan Khan; Muhammad Hassan (Journal of Water Process Engineering, 2023)

Optimizing organizational performance in manufacturing: The role of IT capability, green supply chain integration, and green innovation - Adnan Abbas; Xiaoguang Luo; Fakhar Shahzad; Muhammad Umair Wattoo (Journal of Cleaner Production, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Genome-wide analysis and expression profiling of YUCCA gene family associated with plant vigor in Japanese apricot (prunus mume Sieb. Et zucc) - Faisal Hayat; Yang Bai; Shahid Iqbal; Chengdong Ma; Muhammad Moaaz Ali; Muhammad Adnan Shahid; Mahmood Ul Hasan; Walid F. A. Mosa; Ummara Khan; Huang Xiao; Zhihong Gao (Horticulture, Environment, and Biotechnology, 2023)

Comparative appraisal of groundwater quality in lower and upper riparians of Malir River system through geospatial techniques - Syed Wasi Haider; Syed Jamil Hasan Kazmi; Aamir Alamgir; Adnan Khan; Muhammad Arsalan (Arabian Journal of Geosciences, 2023)

Unveiling the potential of acidified cow dung in combination with plant growth promoting endophytes on growth, physiology, and yield improvement of maize in salt-affected soil - Muhammad Naveed; Rabail Zulekha; Khuram Shehzad Khan; Noman Younas; Muhammad Farhan Qadeer; Martin Brtnicky; Jiri Holatko; Adnan Mustafa (Arabian Journal of Geosciences, 2023)

Sustainable development through corporate social responsibility adoption and its drivers: evidence from corporate industrial sector - Hussain Bux; Zhe Zhang; Muhammad Tayyab Sohail; Naveed Ahmad; Adnan Ali (Environmental Science and Pollution Research, 2023)

Preparation and characterization of single perovskite microplates and its sunlight assisted photodecolorization activity, validated by response surface methodology - Arif Nawaz; Irum Naz; Muhammad Atif; Adnan Khan; Nisar Ali (Chemosphere, 2023)

Microplastic contamination from surface waters and commercially valuable fishes of Karachi Coast, Pakistan - Nazia Arshad; Muhammad Mansoor Alam; Mazliham Bin Mohd Su’ud; Sobia Imran; Tooba Siddiqui; Khadija Saleem; Adnan Bashir; Atia Batool (Regional Studies in Marine Science, 2023)

Biochar alleviated the toxic effects of PVC microplastic in a soil-plant system by upregulating soil enzyme activities and microbial abundance - Attia Rubab Khalid; Tariq Shah; Muhammad Asad; Ahmad Ali; Eisha Samee; Fazal Adnan; Muhammad Faraz Bhatti; Sven Marhan; Claudia I. Kammann; Ghulam Haider (Environmental Pollution, 2023)

Seaweed-derived bio-stimulant improves growth and salt tolerance of radish varieties under saline conditions - Sadaf Gul; Zainul Abideen; Muhammad Yousuf Adnan; Maria Hanif; Muhammad Farrakh Nawaz; Shumaila; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2023)

Phenolic Compounds as a Quality Determinant of Grapes: A Critical Review - Muhammad Shahab; Sergio Ruffo Roberto; Muhammad Adnan; Shah Fahad; Renata Koyama; Muhammad Hamzha Saleem; Jamal Nasar; Shah Saud; Shah Hassan; Taufiq Nawaz (Journal of Plant Growth Regulation, 2023)

Correction: Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efciency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Emerging Field of Nanotechnology in Environment - Vijya Laxmi; Nirjara Singhvi; Nabeel Ahmad; Shruti Sinha; Tripti Negi; Vipin Gupta; Muhammad Mubashshir; Adnan Ahmad; Sandeep Sharma (Indian Journal of Microbiology, 2023)

Integrating low levels of organic fertilizer improves soil fertility and rice yields in paddy fields by influencing microbial communities without increasing CH4 emissions - Anas Iqbal; Xiangru Tang; Izhar Ali; Pengli Yuan; Rayyan Khan; Zaid Khan; Muhammad Adnan; Shanqing Wei; Ligeng Jiang (Applied Soil Ecology, 2023)

Recent insights into pesticide resistance mechanisms in Plutella xylostella and possible management strategies - Muhammad Shehzad; Imran Bodlah; Junaid Ali Siddiqui; Muhammad Adnan Bodlah; Ammara Gull E Fareen; Waqar Islam (Environmental Science and Pollution Research, 2023)

Enhancement of combustion effect leading to improved performance and exhaust emissions of an SI engine with ferrous oxide and graphite nanoparticles - Yasir Hussain Siddiqui; Muhammad Shakaib; Adnan Rasheed; Hafiz Muhammad Ali; Syed Mohammad Rizwan Azeem; Athar Husain Siddique; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Modelling biochemical oxygen demand using improved neuro-fuzzy approach by marine predators algorithm - Rana Muhammad Adnan; Hong-Liang Dai; Ozgur Kisi; Salim Heddam; Sungwon Kim; Christoph Kulls; Mohammad Zounemat-Kermani (Environmental Science and Pollution Research, 2023)
Biochemical oxygen demand (BOD) is one of the most important parameters used for water quality assessment. Alternative methods are essential for accurately prediction of this parameter because the traditional method in predicting the BOD is time-consuming and it is inaccurate due to inconstancies in microbial multiplicity. In this study, the applicability of four hybrid neuro-fuzzy (ANFIS) methods, ANFIS with genetic algorithm (GA), ANFIS with particle swarm optimization (PSO), ANFIS with sine cosine algorithm (SCA), and ANFIS with marine predators algorithm (MPA), was investigated in predicting BOD using distinct input combinations such as potential of hydrogen (pH), dissolved oxygen (DO), electrical conductivity (EC), water temperature (WT), suspended solids (SS), chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (T-P) acquired from two river stations, Gongreung and Gyeongan, South Korea. The applicability of multi-variate adaptive regression spline (MARS) in determination of the best input combination was examined. The ANFIS-MPA was found to be the best model with the lowest root mean square error and mean absolute error and the highest determination coefficient. It improved the root mean square error of ANFIS-PSO, ANFIS-GA, and ANFIS-SCA models by 13.8%, 12.1%, and 6.3% for Gongreung Station and by 33%, 25%, and 6.3% for Gyeongan Station in the test stage, respectively.

Natural resources revenues, shadow economy and financial institutions depth: The way forward - Faryal; Faisal Faisal; Muhammad Yusuf Amin; Zahoor Ul Haq; Sami Ur Rahman; Adnan Ali (Resources Policy, 2023)

Green financing strategy for low-carbon economy: The role of high-technology imports and institutional strengths in China - Taimoor Hassan; Yasir Khan; Adnan Safi; He Chaolin; Salman Wahab; Abdul Daud; Muhammad Tufail (Journal of Cleaner Production, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Enhancing accuracy of extreme learning machine in predicting river flow using improved reptile search algorithm - Rana Muhammad Adnan; Reham R. Mostafa; Hong-Liang Dai; Salim Heddam; Adil Masood; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2023)

Efficacy of γ-Aminobutyric Acid (GABA) on Physio-biochemical Attributes of Lettuce (Lactuca sativa L.) Under Cadmium Toxicity - Zainab Waris; Zahra Noreen; Anis Ali Shah; Sheeraz Usman; Adnan Noor Shah; Muhammad Rizwan; Ryan Casini; Hosam O. Elansary (Journal of Plant Growth Regulation, 2023)

Ascorbic and Salicylic Acids Vitalized Growth, Biochemical Responses, Antioxidant Enzymes, Photosynthetic Efficiency, and Ionic Regulation to Alleviate Salinity Stress in Sorghum bicolor - Muhammad Azeem; Robina Sultana; Athar Mahmood; Muhammad Qasim; Zamin Shaheed Siddiqui; Sahar Mumtaz; Talha Javed; Muhammad Umar; M. Yousuf Adnan; Manzer H. Siddiqui (Journal of Plant Growth Regulation, 2023)

Trehalose: A Key Player in Plant Growth Regulation and Tolerance to Abiotic Stresses - Muhammad Umair Hassan; Muhammad Nawaz; Adnan Noor Shah; Ali Raza; Lorenzo Barbanti; Milan Skalicky; Mohamed Hashem; Marian Brestic; Saurabh Pandey; Saad Alamri; Yasser S. Mostafa; Ayman E. L. Sabagh; et al. (Journal of Plant Growth Regulation, 2023)

Daidzein attenuated paclitaxel-induced neuropathic pain via the down-regulation of TRPV1/P2Y and up-regulation of Nrf2/HO-1 signaling - Sana Zafar; Yong Luo; Li Zhang; Chang Hu Li; Adnan Khan; Muhammad Ibrar Khan; Kifayatullah Shah; Eun Kyoung Seo; Feng Wang; Salman Khan (Inflammopharmacology, 2023)

The role of eco-innovation, renewable energy consumption, economic risks, globalization, and economic growth in achieving sustainable environment in emerging market economies - Qazi Muhammad Adnan Hye; Jabbar Ul-Haq; Hubert Visas; Raja Rehan (Environmental Science and Pollution Research, 2023)

Chemical composition and antimicrobial activity of Boswellia serrata oleo-gum-resin essential oil extracted by superheated steam - Muhammad Adnan Ayub; Muhammad Asif Hanif; Joanne Blanchfield; Muhammad Zubair; Muhammad Amin Abid; Muhammad Tahir Saleh (Natural Product Research, 2023)

Economic and non-economic drivers of tourism: bidirectional causality of tourism and environment for South Asian economies - Salman Wahab; Bilal Ahmed; Muhammad Imran; Adnan Safi; Zeeshan Wahab (Environmental Science and Pollution Research, 2023)

Multifunctional catalyst-assisted sustainable reformation of lignocellulosic biomass into environmentally friendly biofuel and value-added chemicals - Muhammad Naeem; Muhammad Imran; Shoomaila Latif; Adnan Ashraf; Nazim Hussain; Grzegorz Boczkaj; Wojciech Smułek; Teofil Jesionowski; Muhammad Bilal (Chemosphere, 2023)

Nickel (Ni) phytotoxicity and detoxification mechanisms: A review - Adnan Mustafa; Usman Zulfiqar; Muhammad Zahid Mumtaz; Maja Radziemska; Fasih Ullah Haider; Jiri Holatko; Tereza Hammershmiedt; Muhammad Naveed; Hassan Ali; Antonin Kintl; Qudsia Saeed; Jiri Kucerik; et al. (Chemosphere, 2023)

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

Testing of Magnetic ZnO/MgFe2O4 Heterostructures for Photocatalytic Removal of Synthetic Dye Pollutants from Wastewater - Muhammad Shoaib; Muhammad Adnan Munir; Muhammad Yasin Naz; Ghulam Abbas; Muhammad Irfan; Saifur Rahman; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

A two-stage interval-valued carbon price forecasting model based on bivariate empirical mode decomposition and error correction - Piao Wang; Muhammad Adnan Zahid Chudhery; Jilan Xu; Xin Zhao; Chen Wang (Environmental Science and Pollution Research, 2023)

Optimized photodegradation of palm oil agroindustry waste effluent using multivalent manganese–modified black titanium dioxide - Rab Nawaz; Sajjad Haider; Muzammil Anjum; Vipin Kumar Oad; Adnan Haider; Rawaiz Khan; Muhammad Aqif; Tahir Hanif; Nasruulah Khan (Environmental Science and Pollution Research, 2023)

Exogenous application of glutathione and gamma amino-butyric acid alleviates salt stress through improvement in antioxidative defense system and modulation of CaXTHs stress-related genes - Musarrat Ramzan; Anis Ali Shah; Muhammad Zaheer Ahmed; Muhammad Adnan Bukhari; Liaqat Ali; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

Breaking down the complexity of sustainable development: A focus on resources, economic complexity, and innovation - Adnan Safi; Xin Wei; Eduard Montesinos Sansaloni; Muhammad Umar (Resources Policy, 2023)

Mapping environmental sustainability of knitted textile production facilities - Md. Shamsuzzaman; Md Mazedul Islam; H M Rakib Ul Hasan; Adnan Maroof Khan; Abu Sadat Muhammad Sayem (Journal of Cleaner Production, 2023)

Engineering of oxygen vacancy defect in CeO2 through Mn doping for toluene catalytic oxidation at low temperature - Ahmed Ismail; Muhammad Zahid; Sharafat Ali; Syed ul Hasnain Bakhtiar; Nauman Ali; Adnan Khan; Yujun Zhu (Environmental Research, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

Potassium-Nitrogen Ratio Improved Cotton Yield by Regulating Antioxidant Metabolism Under a New Cropping Model for the Yangtze River Valley of China - Saif Ali; Abdul Hafeez; Xiaolei Ma; Shahbaz Atta Tung; Muhammad Sohaib Chattha; Shoaib Ahmad; Adnan Noor Shah; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2023)

Effects of Winter Cropping on rice Yield, Economic Benefit, and Resource Utilization Efficiency on Different Cropping Systems of Paddy Field in the Middle Reaches of the Yangtze River - Haiying Tang; Guiyuan Meng; Wenjie Jiang; Ying Liu; Athar Mahmood; Adnan Noor Shah; Muhammad Nawaz; Muhammad Umair Hassan; Guoqin Huang (International Journal of Plant Production, 2023)

Arsenic Speciation in Rice, Mechanisms and Associated Health Risk Through Rice Consumption in Various Districts of Khyber Pakhtunkhwa, Pakistan - Tasneem Sarwar; Sardar Khan; Javed Nawab; Said Muhammad; Shehla Amin; Janas Khan; Adnan Sarwar; Iqbal Haider; Qing Huang (Exposure and Health, 2023)

Improving Significant Wave Height Prediction Using a Neuro-Fuzzy Approach and Marine Predators Algorithm - Rana Muhammad Adnan Ikram; Xinyi Cao; Tayeb Sadeghifar; Alban Kuriqi; Ozgur Kisi; Shamsuddin Shahid (Journal of Marine Science and Engineering, 2023)
This study investigates the ability of a new hybrid neuro-fuzzy model by combining the neuro-fuzzy (ANFIS) approach with the marine predators’ algorithm (MPA) in predicting short-term (from 1 h ahead to 1 day ahead) significant wave heights. Data from two stations, Cairns and Palm Beach buoy, were used in assessing the considered methods. The ANFIS-MPA was compared with two other hybrid methods, ANFIS with genetic algorithm (ANFIS-GA) and ANFIS with particle swarm optimization (ANFIS-PSO), in predicting significant wave height for multiple lead times ranging from 1 h to 1 day. The multivariate adaptive regression spline was investigated in deciding the best input for prediction models. The ANFIS-MPA model generally offered better accuracy than the other hybrid models in predicting significant wave height in both stations. It improved the accuracy of ANFIS-PSO and ANFIS-GA by 8.3% and 11.2% in root mean square errors in predicting a 1 h lead time in the test period.

Novel evolutionary-optimized neural network for predicting landslide susceptibility - Rana Muhammad Adnan Ikram; Imran Khan; Hossein Moayedi; Atefeh Ahmadi Dehrashid; Ismail Elkhrachy; Binh Nguyen Le (Environment, Development and Sustainability, 2023)

Zinc oxide nanoparticles coated urea enhances nitrogen efficiency and zinc bioavailability in wheat in alkaline calcareous soils - Shaiza Amin; Tariq Aziz; Muhammad Zia-ur-Rehman; Ifra Saleem; Muhammad Rizwan; Ambreen Ashar; Hafiz Adnan Mussawar; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2023)

Antibiotics induced changes in nitrogen metabolism and antioxidative enzymes in mung bean (Vigna radiata) - Marium Fiaz; Iftikhar Ahmed; Sumara Masood Ul Hassan; Adnan Khan Niazi; Muhammad Fahim Khokhar; Zeshan; Muhammad Ansar Farooq; Muhammad Arshad (Science of The Total Environment, 2023)

How China is mitigating resource curse through infrastructural development? - Xiangfeng Ji; Tianyu Song; Muhammad Umar; Adnan Safi (Resources Policy, 2023)

A review on covalent organic frameworks as adsorbents for organic pollutants - Awais Ali Aslam; Adnan Irshad; Muhammad Shahid Nazir; Muhammad Atif (Journal of Cleaner Production, 2023)

Withametelin, a steroidal lactone, isolated from datura innoxa attenuates STZ-induced diabetic neuropathic pain in rats through inhibition of NF-kB/MAPK signaling - Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Muhammad Waleed Baig; Ihsan ul Haq; Salman Khan (Food and Chemical Toxicology, 2023)

A novel swarm intelligence: cuckoo optimization algorithm (COA) and SailFish optimizer (SFO) in landslide susceptibility assessment - Rana Muhammad Adnan Ikram; Atefeh Ahmadi Dehrashid; Binqiao Zhang; Zhihuan Chen; Binh Nguyen Le; Hossein Moayedi (Stochastic Environmental Research and Risk Assessment, 2023)

Transition to greener electricity and resource use impact on environmental quality: Policy based study from OECD countries - Muhammad Adnan Bashir; Zhao Dengfeng; Fouzia Amin; Grzegorz Mentel; Syed Ali Raza; Muhammad Farhan Bashir (Utilities Policy, 2023)

Vegetable oils as bio-based precursors for epoxies - Fareeha Marriam; Adnan Irshad; Isra Umer; Muhammad Arslan Asghar; Muhammad Atif (Sustainable Chemistry and Pharmacy, 2023)

Wild food plants gathered by four cultural groups in North Waziristan, Pakistan - Noor Khalid; Lal Badshah; Adnan Ali Shah; Arman Ullah; Naushad Khan; Muhammad Abdul Aziz; Renata Sõukand; Andrea Pieroni (Genetic Resources and Crop Evolution, 2023)

Plant-soil-microbe interactions in maintaining ecosystem stability and coordinated turnover under changing environmental conditions - Muhammad Aqeel; Jinzhi Ran; Weigang Hu; Muhammad Kashif Irshad; Longwei Dong; Muhammad Adnan Akram; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Lai Fatt Chuah; Jianming Deng (Chemosphere, 2023)

Tissue specific expression of bacterial cellulose synthase (Bcs) genes improves cotton fiber length and strength - Sidra Akhtar; Ahmad Ali Shahid; Sana Shakoor; Mukhtar Ahmed; Sehrish Iftikhar; Muhammad Usmaan; Sahar Sadaqat; Ayesha Latif; Adnan Iqbal; Abdul Qayyum Rao (Plant Science, 2023)

Short-term probabilistic prediction of significant wave height using bayesian model averaging: Case study of chabahar port, Iran - Rana Muhammad Adnan; Tayeb Sadeghifar; Meysam Alizamir; Masouad Torabi Azad; Oleg Makarynskyy; Ozgur Kisi; Reza Barati; Kaywan Othman Ahmed (Ocean Engineering, 2023)

Detection and quantification of aflatoxins in spices stored in different food packaging materials - Muhammad Abrar; Samreen Ahsan; Muhmmad Nadeem; Atif Liaqat; Muhmmad Farhan Jahangir Chughtai; Muhammad Adil Farooq; Tariq Mehmood; Adnan Khaliq; Ayesha Siddiqa (Journal of Stored Products Research, 2023)

Bombax ceiba flower extract mediated synthesis of Se nanoparticles for antibacterial activity and urea detection - Muhammad Safdar; Sidra Aslam; Misbah Akram; Adnan Khaliq; Samreen Ahsan; Atif Liaqat; Misbah Mirza; Muhammad Waqas; Waseem Akhtar Qureshi (World Journal of Microbiology and Biotechnology, 2023)

Triticum aestivum: antioxidant gene profiling and morpho-physiological studies under salt stress - Musarrat Ramzan; Memoona Gillani; Anis Ali Shah; Adnan Noor Shah; Naheed Kauser; Muhammad Jamil; Rana Touqeer Ahmad; Sami Ullah (Molecular Biology Reports, 2023)

Plant microbe mediated enhancement in growth and yield of canola (Brassica napus L.) plant through auxin production and increased nutrient acquisition - Misha Iqbal; Muhammad Naveed; Muhammad Sanaullah; Martin Brtnicky; M. Iftikhar Hussain; Jiri Kucerik; Jiri Holatko; Adnan Mustafa (Journal of Soils and Sediments, 2023)

Identification of shoot and root genomic regions in response to nitrogen deficiency tolerance in rice through the use of rice back cross recombinant inbred lines (BRILs) - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Huijie Li; Saba Khanzada; Muhammad Faheem; Mashooq Ali Laghari; Jianmin Bian; Xiaohua Pan; Ziming Wu (Journal of Plant Biochemistry and Biotechnology, 2023)

The impact of brick kilns on environment and society: a bibliometric and thematic review - Muhammad Arham Parvez; Irfan Ahmad Rana; Adnan Nawaz; Hafiz Syed Hamid Arshad (Environmental Science and Pollution Research, 2023)

Development of reusable chitosan-supported nickel sulfide microspheres for environmentally friendlier and efficient bio-sorptive decontamination of mercury toxicant - Yonghong Han; Juan Tao; Adnan Khan; Afrasiab Khan; Nisar Ali; Sumeet Malik; Chunhao Yu; Yong Yang; Teofil Jesionowski; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Cellulose/inorganic nanoparticles-based nano-biocomposite for abatement of water and wastewater pollutants - Zhen Zhang; Abdulrazaq Ibrahim Said Ahmed; Muhammad Zeeshan Malik; Nisar Ali; Adnan khan; Farman Ali; Mohamed Osman Hassan; Badr A. Mohamed; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Recyclable Cu–Ag bimetallic nanocatalyst for radical scavenging, dyes removal and antimicrobial applications - Faisal Ali; Sadia Akbar; Mika Sillanpaa; Umer Younas; Adnan Ashraf; Muhammad Pervaiz; Rizwan Kausar; Ikram Ahmad; Asma A. Alothman; Mohamed Ouladsmane (Chemosphere, 2023)

Physiological and transcriptome analyses demonstrate the silver nanoparticles mediated alleviation of salt stress in pearl millet (Pennisetum glaucum L) - Imran Khan; Samrah Afzal Awan; Muhammad Rizwan; Muhammad Adnan Akram; Muhammad Zia-ur-Rehman; Xiaosan Wang; Xinquan Zhang; Linkai Huang (Environmental Pollution, 2023)

Water Temperature Prediction Using Improved Deep Learning Methods through Reptile Search Algorithm and Weighted Mean of Vectors Optimizer - Rana Muhammad Adnan Ikram; Reham R. Mostafa; Zhihuan Chen; Kulwinder Singh Parmar; Ozgur Kisi; Mohammad Zounemat-Kermani (Journal of Marine Science and Engineering, 2023)
Precise estimation of water temperature plays a key role in environmental impact assessment, aquatic ecosystems’ management and water resources planning and management. In the current study, convolutional neural networks (CNN) and long short-term memory (LSTM) network-based deep learning models were examined to estimate daily water temperatures of the Bailong River in China. Two novel optimization algorithms, namely the reptile search algorithm (RSA) and weighted mean of vectors optimizer (INFO), were integrated with both deep learning models to enhance their prediction performance. To evaluate the prediction accuracy of the implemented models, four statistical indicators, i.e., the root mean square errors (RMSE), mean absolute errors, determination coefficient and Nash–Sutcliffe efficiency were utilized on the basis of different input combinations involving air temperature, streamflow, precipitation, sediment flows and day of the year (DOY) parameters. It was found that the LSTM-INFO model with DOY input outperformed the other competing models by considerably reducing the errors of RMSE and MAE in predicting daily water temperature.

One-pot solvothermal synthesis of highly catalytic Janus transition metal phosphides (TMPs) for high performance OER - Zeenat; Zahoor Ahmad; Adnan Maqbool; Muhammad Asif Hussain; Rami Adel Pashameah; Amber Shahzadi; Nosheen Nazar; Shahid Iqbal; Abdullah K. Alanazi; Muhammad Naeem Ashiq; Hala M. Abo-Dief (Fuel, 2023)

Physically separated soil organic matter pools as indicators of carbon and nitrogen change under long-term fertilization in a Chinese Mollisol - Adnan Mustafa; Qudsia Saeed; Mohammad Tahsin Karimi Nezhad; Sun Nan; Gao Hongjun; Zhu Ping; Muhammad Naveed; Xu Minggang; Avelino Nú nez-Delgado (Environmental Research, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Exploring the role of economic and institutional indicators for carbon and GHG emissions: policy-based analysis for OECD countries - Muhammad Adnan Bashir; Zhao Dengfeng; Muhammad Farhan Bashir; Syed Rahim; Zhang Xi (Environmental Science and Pollution Research, 2022)

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Protective Mechanisms of Melatonin Against Vanadium Phytotoxicity in Tomato Seedlings: Insights into Nutritional Status, Photosynthesis, Root Architecture System, and Antioxidant Machinery - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Latif Ullah Khan; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Muhammad Azher Nawaz; Safina Naz; Sidra Shahid; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Adnan Shahid (Journal of Plant Growth Regulation, 2022)

Nanoparticle’s uptake and translocation mechanisms in plants via seed priming, foliar treatment, and root exposure: a review - Imran Khan; Samrah Afzal Awan; Muhammad Rizwan; Zaid Ul Hassan; Muhammad Adnan Akram; Rezwan Tariq; Marian Brestic; Wengang Xie (Environmental Science and Pollution Research, 2022)

Exploration of solid waste materials for sustainable manufacturing of cementitious composites - Hamayun Khan; Anwar Baig; Mahtab Faisal; Adnan Khan; Kashif Gul; Nauman Ali; Nisar Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Evaluation and projection of precipitation in Pakistan using the Coupled Model Intercomparison Project Phase 6 model simulations - Adnan Abbas; Safi Ullah; Waheed Ullah; Muhammad Waseem; Xin Dou; Chengyi Zhao; Aisha Karim; Jianting Zhu; Daniel Fiifi Tawia Hagan; Asher Samuel Bhatti; Gohar Ali (International Journal of Climatology, 2022)
This study aimed to evaluate the performance of global climate models (GCMs) from the family of the Coupled Model Intercomparison Project Phase 6 (CMIP6) in the historical simulation of precipitation and select the best performing GCMs for future projection of precipitation in Pakistan under multiple shared socioeconomic pathways (SSPs). The spatiotemporal performance of GCMs was evaluated against the Climate Research Unit (CRU) data in simulating annual precipitation during 1951–2014, using the Taylor diagram and interannual variability skill (IVS). Moreover, the modified Mann–Kendall (mMK) and Sen's slope estimator (SSE) tests were employed to estimate significant trends in future precipitation for the period 2015–2100. Based on the comprehensive ranking index (CRI), the HadGEM3‐GC31‐MM model has the highest skill in simulating precipitation distributions followed by EC‐Earth3‐Veg‐LR, CNRM‐ESM2‐1, MPI‐ESM1‐2‐HR, CNRM‐CM6‐1, MRI‐ESM2‐0, CNRM‐CM6‐1‐HR, EC‐Earth3‐Veg, MCM‐UA‐1‐0, INM‐CM5‐0, KACE‐1‐0‐G, CAMS‐CSM1‐0, and HadGEM3‐GC31‐LL models. Furthermore, the projections of the best models ensemble mean (BMEM) showed that the study region will experience a substantial increase in precipitation under SSP3‐7.0 and SSP5‐8.5 but an indolent rise under SSP1‐2.6 and SSP2‐4.5 scenarios. The summer and annual precipitations exhibit a statistically significant increasing trend relative to the winter season under most scenarios. Moreover, the magnitude of monotonic trends in seasonal and annual precipitation progresses from low forcing scenario (SSP1‐2.6) to high forcing scenario (SSP5‐8.5). The findings of the study could provide a benchmark in selecting appropriate GCMs for future projection over a data scare region, like Pakistan. Moreover, the projected trends of future precipitation are crucial in devising adaption and mitigation actions towards sustainable planning of water resource management, food security, and disaster risk management.

Biological and Photocatalytic Degradation of Congo Red, a Diazo Sulfonated Substituted Dye: a Review - Rana Rashad Mahmood Khan; Hoorish Qamar; Ayesha Hameed; Aqmar ur Rehman; Muhammad Pervaiz; Zohaib Saeed; Aqib Adnan; Ayoub Rashid Ch (Water, Air, & Soil Pollution, 2022)

Sensitivity analysis of greenhouse gas emissions at farm level: case study of grain and cash crops - Adnan Abbas; Muhammad Waseem; Riaz Ahmad; Khurshied Ahmed khan; Chengyi Zhao; Jianting Zhu (Environmental Science and Pollution Research, 2022)

Capturing spatial variability of factors affecting the water allocation plans—a geo-informatics approach for large irrigation schemes - Muhammad Mohsin Waqas; Muhammad Waseem; Sikandar Ali; Jan W. Hopman; Usman Khalid Awan; Syed Hamid Hussain Shah; Adnan Noor Shah (Environmental Science and Pollution Research, 2022)

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Does geothermal energy and natural resources affect environmental sustainability? Evidence in the lens of sustainable development - Muhammad Adnan Bashir; Zhao Dengfeng; Irum Shahzadi; Muhammad Farhan Bashir (Environmental Science and Pollution Research, 2022)

A Comprehensive Review About Bioactive Peptides: Sources to Future Perspective - Muhammad Naeem; Muhammad Inamullah Malik; Talha Umar; Swaiba Ashraf; Adnan Ahmad (International Journal of Peptide Research and Therapeutics, 2022)

Variation in Vortex-Induced Vibration Phenomenon Due to Surface Roughness on Low- and High-Mass-Ratio Circular Cylinders: A Numerical Study - Muhammad Usman Anwar; Niaz Bahadur Khan; Muhammad Arshad; Adnan Munir; Muhammad Nasir Bashir; Mohammed Jameel; Muhammad Faisal Rehman; Sayed M. Eldin (Journal of Marine Science and Engineering, 2022)
Fluid–structure interaction has been widely studied in the last few decades due to its wide range of applications in engineering fields. This phenomenon plays an important design role, for example, in offshore risers, high slender buildings, chimney stacks and heat exchangers. The vortex shedding generated from a bluff body can induce high-amplitude oscillations, known as vortex-induced vibrations (VIVs). This study presents a numerical analysis to investigate the impact of surface roughness on VIV in the crossflow direction of a circular cylinder. The study also investigates the impact of surface roughness with variation in mass ratio from 2.4 to 11 at a high Reynolds number (Re) = 104 using Reynolds-averaged Navier–Stokes (RANS) equations. The study concludes that roughness on a cylinder results in a reduction in amplitude response. Furthermore, the lock-in region is narrower compared to that of a smooth cylinder, irrespective of the mass ratio. However, it is observed that the impact of surface roughness is more significant in high-mass-ratio cylinders where the lock-in region is more squeezed and shifted toward lower reduced velocities. Furthermore, the vortex mode beyond reduced velocities Ur = 5.84 and 7.52 was observed to be 2S for high and low mass ratios, respectively.

Robust segmentation of underwater fish based on multi-level feature accumulation - Adnan Haider; Muhammad Arsalan; Jiho Choi; Haseeb Sultan; Kang Ryoung Park (Frontiers in Marine Science, 2022)
Because fish are vital to marine ecosystems, monitoring and accurate detection are crucial for assessing the potential for fisheries in these environments. Conventionally, fish-related assessment is conducted manually, which makes it labor-intensive and time-consuming. In addition, the assessments are challenging owing to underwater visibility limitations, which leads to poor detection accuracy. To overcome these problems, we propose two novel architectures for the automatic and high-performance segmentation of fish populations. In this study, the efficient fish segmentation network (EFS-Net) and multi-level feature accumulation-based segmentation network (MFAS-Net) are the base and final networks, respectively. In deep convolutional neural networks, the initial layers usually contain potential spatial information. Therefore, the EFS-Net employs a series of convolution layers in the early stage of the network for optimal feature extraction. To boost segmentation accuracy, the MFAS-Net uses an initial feature refinement and transfer block to refine potential low-level information and subsequently transfers it to the deep stages of the network. Moreover, the MFAS-Net employs multi-level feature accumulation that improves pixel-wise prediction for fish that are indistinct. The proposed networks are evaluated using two publicly available datasets, namely DeepFish and semantic segmentation of underwater imagery (SUIM), both of which contain challenging underwater fish segmentation images. The experimental results reveal that mean intersection-over-unions of 76.42% and 92.0% are attained by the proposed method for the DeepFish and SUIM datasets, respectively; these values are higher than those by the state-of-the-art methods such as A-LCFCN+PM and DPANet. In addition, high segmentation performance is achieved without compromising the computational efficiency of the networks. The MFAS-Net requires only 3.57 million trainable parameters to be fully trained. The proposed model and the complete code will be made available 1 .

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Synthesis, characterization and biological evaluation of Bis-benzimidazolium salts and their silver(I)-N-heterocyclic carbene complexes - Rana Yasir Nadeem; Munazzah Yaqoob; WanSinn Yam; Rosenani A. Haque; Muhammad Adnan Iqbal (Medicinal Chemistry Research, 2022)

An active learning method for diabetic retinopathy classification with uncertainty quantification - Muhammad Ahtazaz Ahsan; Adnan Qayyum; Adeel Razi; Junaid Qadir (Medical & Biological Engineering & Computing, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

RETRACTED ARTICLE: Investigation on the role of graphene-based composites for in photocatalytic degradation of phenol-based compounds in wastewater: a review - Shumila Shaheen; Rana Rashad Mahmood Khan; Awais Ahmad; Rafael Luque; Muhammad Pervaiz; Zohaib Saeed; Ahmad Adnan (Environmental Science and Pollution Research, 2022)

Effects of ash derived from livestock manure and two other treatments on soil moisture content and water infiltration rate - Fatemehsadat Mortazavizadeh; Amirali Fatahi; Keyvan Asefpour Vakilian; Paulo H. Pagliari; Artemi Cerdà; Majid Mirzaei; Xiuju Zhang; Rana Muhammad Adnan Ikram (Irrigation and Drainage, 2022)
This study investigates the effects of using livestock manure (LM), livestock manure ash (LMA) and the combination of LM with LMA (LM + LMA) on the soil moisture content and water infiltration rate of clay, clay loam and sandy loam soils. The soil moisture content and water infiltration rate were 11.60, 8.90 and 6.85% and 1.98, 1.55 and 1.62 cm h‾¹ for clay, clay loam and sandy loam soils, respectively, by the application of 15 t ha‾¹ LM. Moreover, using 15 t ha‾¹ of LMA had the most desirable effects on the soil moisture content in the clay and clay loam soils. Using this treatment, the soil moisture content and water infiltration rate were 10.85, 11.20 and 7.24% and 2.40, 1.90 and 1.75 cm h‾¹ for clay, clay loam and sandy loam soils, respectively. Promising results were obtained using 15 + 15 t ha‾¹ of LM + LMA, where the soil moisture content and water infiltration rate were 11.50, 10.20 and 8.20% and 2.80, 1.90 and 1.72 cm h‾¹ for clay, clay loam and sandy loam soils, respectively. Both LMA and its combination with LM were found to be positive strategies to achieve sustainable agricultural goals because of the increased water infiltrates (less runoff) available for the plants.

Characterization and Utilization of Cow Manure Biochar as Soil Amendment for the Management of Northern Corn Leaf Blight - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Adnan Akhter; Tehmina Bahar; Waheed Anwar; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2022)

Robust bioinspired surfaces and their exploitation for petroleum hydrocarbon remediation - Nisar Ali; Essoh Lionnelle Gyllye; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections - Irfan Ur Rashid; Muhammad Adnan Abid; Mansour Almazroui; Fred Kucharski; Muhammad Hanif; Shaukat Ali; Muhammad Ismail (International Journal of Climatology, 2022)
Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in net shortwave radiation that leads to extreme surface warming over the region. Moreover, the El Niño–Southern Oscillation (ENSO) based on Niño3.4 SST index is negatively associated with SAT anomalies over Pakistan. The cold ENSO phase favours the positive geopotential height anomalies due to the strengthening of the Walker circulation that enhance the sinking motion and result in less cloudiness leading to the extreme higher surface temperature conditions over Pakistan, while the opposite happens in the warm ENSO phase. Moreover, the Saudi‐KAU Atmospheric Global Climate Model (AGCM) simulated large‐scale patterns that are in good agreement with the observations. Sensitivity experiments with the AGCM confirm that cold SST anomalies in the ENSO region significantly favour above‐normal SAT anomalies over Pakistan, while the opposite happens in the warm ENSO phase. These results are important to understand and potentially predict regional heatwaves over the South Asian region, particularly over Pakistan.

Effect of Variation in the Mass Ratio on Vortex-Induced Vibration of a Circular Cylinder in Crossflow Direction at Reynold Number = 104: A Numerical Study Using RANS Model - Muhammad Usman Anwar; Maha M. A. Lashin; Niaz B. Khan; Adnan Munir; Mohammed Jameel; Riaz Muhammad; Kamel Guedri; Ahmed M. Galal (Journal of Marine Science and Engineering, 2022)
This study reports on the numerical analysis of the impact of mass ratio on the Vortex-Induced Vibration (VIV) phenomenon of an elastically rigid cylinder, oscillating freely in a crossflow direction. Reynolds-averaged Navier–Stokes (RANS) equations with (k-ω SST) model were used to analyze the flow behavior, amplitude ratio and vortex shedding patterns. The study was performed at constant Reynold number (Re) = 104 with reduced velocity (Ur) ranging from 2 to 14 and mass ratio (m*) of 2.4 and 11. The mass ratio was defined as the ratio between mass of the vibrating cylinder and mass of the fluid displaced. It was found that increasing the mass ratio from 2.4 to 11 resulted in decrease in amplitude response by 80%, 71% and 31% at initial branch, upper to lower transition region and lower branch, respectively. However, the amplitude in the upper branch decreased only 8% at high mass ratio. The peak amplitude observed in the present study was lower than previous experimental and DES results. However, the RANS k-ω SST well captured the vortex shedding modes of 2S, 2P, P + S, and 2T. In 2S mode, two single pairs of vortices were formed, whereas in 2P mode two pairs were generated in single oscillation. Similarly, P + S meant one pair and one individual vortex; whereas 2T mode meant two triplets of vortices generated in one oscillation. The study concluded that increase in mass ratio results in shortening of the lock-in region and decrease in amplitude response.

Synergetic Efficacy of Amending Pb-Polluted Soil with P-Loaded Jujube (Ziziphus mauritiana) Twigs Biochar and Foliar Chitosan Application for Reducing Pb Distribution in Moringa Leaf Extract and Improving Its Anti-cancer Potential - Bilal Rasool; Mahmood-ur-Rahman; Muhammad Zubair; Muhammad Asaf Khan; Pia Muhammad Adnan Ramzani; Agnieszka Dradrach; Veysel Turan; Muhammad Iqbal; Shahbaz Ali Khan; Hafiz Muhammad Tauqeer; Muniba Farhad; Zaheer Abbas Virk; et al. (Water, Air, & Soil Pollution, 2022)

Performance evaluation and comparison of observed and reanalysis gridded precipitation datasets over Pakistan - Sayed Waseem Iqbal; Muhammad Latif; Rehan Ahmed; Shahzada Adnan; Muhammad Umar; Burhan Ahmad; Muhammad Azam; Jabir Hussain Syed (Theoretical and Applied Climatology, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Water quality and health risk assessment of trace elements in surface water at Punjnad Headworks, Punjab, Pakistan - Saima Naz; Borhan Mansouri; Ahmad Manan Mustafa Chatha; Qudrat Ullah; Zain Ul Abadeen; Muhammad Zahoor Khan; Adnan Khan; Saba Saeed; Rayees Ahmad Bhat (Environmental Science and Pollution Research, 2022)

Hazardous wastes, adverse impacts, and management strategies: a way forward to environmental sustainability - Guoqing Qian; Chuansong Duanmu; Nisar Ali; Adnan Khan; Sumeet Malik; Yong Yang; Muhammad Bilal (Environment, Development and Sustainability, 2022)

The nexus between traditional foraging and its sustainability: a qualitative assessment among a few selected Eurasian case studies - Muhammad Abdul Aziz; Giulia Mattalia; Naji Sulaiman; Adnan Ali Shah; Zbynek Polesny; Raivo Kalle; Renata Sõukand; Andrea Pieroni (Environment, Development and Sustainability, 2022)

Role of financial stability, technological innovation, and renewable energy in achieving sustainable development goals in BRICS countries - Salman Wahab; Muhammad Imran; Adnan Safi; Zeeshan Wahab; Dervis Kirikkaleli (Environmental Science and Pollution Research, 2022)

Involvement of VIVID in white light‐responsive pigmentation, sexual development and sterigmatocystin biosynthesis in the filamentous fungus Podospora anserina - Ling Shen; Florence Chapeland‐Leclerc; Gwenaël Ruprich‐Robert; Qiyi Chen; Siyu Chen; Muhammad Adnan; Jiangxin Wang; Gang Liu; Ning Xie (Environmental Microbiology, 2022)
Summary Light serves as a source of information and regulates diverse physiological processes in living organisms. Fungi perceive and respond to light through a complex photosensory system. Fungi have evolved the desensitization mechanism to adapt to the changing light signal in a natural environment. White light exerts multiple essential impacts on the model filamentous fungus Podospora anserina . However, the light sensing and response in this species has not been investigated. In this study, we demonstrated that the loss of function of the light desensitization protein VIVID (VVD) in P. anserina triggered exacerbated light responses and therefore led to drastic morphological and physiological changes. The white light‐sensitive mutant Δ vvd showed growth reduction, spermatia overproduction, enhanced hyphae pigmentation and reduced oxidative stress tolerance. We observed the decreased expression level of sterigmatocystin gene cluster by transcriptome analysis and finally detected the reduced production of sterigmatocystin in Δ vvd in response to white light. Our data indicate that VVD acts as a repressor of white collar complex. This study exhibits a vital role of VVD in governing white light‐responsive gene expression and secondary metabolite production and contributes to a better understanding of the photoreceptor VVD in P. anserina .

Carbon and nitrogen metabolism in peach trees on different Prunus rootstocks in response to flooding - Trequan McGee; Bruce Schaffer; Muhammad Adnan Shahid; Jose X. Chaparro; Ali Sarkhosh (Plant and Soil, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

CRISPR/Cas9 is a powerful tool for precise genome editing of legume crops: a review - Adnan Rasheed; Aminah A. Barqawi; Athar Mahmood; Muhammad Nawaz; Adnan Noor Shah; Daniyah H. Bay; Maryam A. Alahdal; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Prospect of Anterior Gradient 2 homodimer inhibition via repurposing FDA-approved drugs using structure-based virtual screening - Shafi Ullah; Shafi Ullah Khan; Abbas Khan; Muhammad Junaid; Humaira Rafiq; Thet Thet Htar; Yaxue Zhao; Syed Adnan Ali Shah; Abdul Wadood (Molecular Diversity, 2022)

Influences of Long-term Crop Cultivation and Fertilizer Management on Soil Aggregates Stability and Fertility in the Loess Plateau, Northern China - Farhat Ullah Khan; Adnan Anwar Khan; Kai Li; Xuexuan Xu; Muhammad Adnan; Shah Fahad; Rafiq Ahmad; Mushtaq Ahmad Khan; Taufiq Nawaz; Faisal Zaman (Journal of Soil Science and Plant Nutrition, 2022)

Screening of Rice Cultivars for Nitrogen Use Efficiency and Yield Stability under Varying Nitrogen Levels - Weilu Wang; Liying Huang; Guanglong Zhu; Hao Zhang; Zhiqin Wang; Muhammad Adnan; Shah Saud; Zafar Hayat; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Advanced research tools for fungal diversity and its impact on forest ecosystem - Muhammad Adnan; Waqar Islam; Liu Gang; Han Y. H. Chen (Environmental Science and Pollution Research, 2022)

An outlook on the development of renewable energy, policy measures to reshape the current energy mix, and how to achieve sustainable economic growth in the post COVID-19 era - Muhammad Farhan Bashir; Muhammad Sadiq; Besma Talbi; Luqman Shahzad; Muhammad Adnan Bashir (Environmental Science and Pollution Research, 2022)

Integrating green business strategies and green competencies to enhance green innovation: evidence from manufacturing firms of Pakistan - Salman Yahya; Adnan Khan; Maryam Farooq; Muhammad Irfan (Environmental Science and Pollution Research, 2022)

Prospects of Multiproduct Algal Biorefineries Involving Cascading Processing of the Biomass Employing a Zero-Waste Approach - Sana Malik; Ayesha Shahid; Muhammad Nabeel Haider; Mahwish Amin; Michael J. Betenbaugh; Muhammad Aamer Mehmood; Muhammad Adnan Ul Haq; Achmad Syafiuddin; Raj Boopathy (Current Pollution Reports, 2022)

Exploring the potential of Eocene carbonates through petrographic, geochemical, and geotechnical analyses for their utilization as aggregates for engineering structures - Abdul Rahim Asif; Ihtisham Islam; Waqas Ahmed; Muhammad Sajid; Adnan Qadir; Allah Ditta (Arabian Journal of Geosciences, 2022)

Identifying impact of international trade and renewable energy consumption on environmental quality improvement and their role in global warming - Arshad Ahmad Khan; Sufyan Ullah Khan; Muhammad Abu Sufyan Ali; Adnan Safi; Yuling Gao; Jianchao Luo (Environmental Science and Pollution Research, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Correction to: Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2022)

Development of new machine learning model for streamflow prediction: case studies in Pakistan - Rana Muhammad Adnan; Reham R. Mostafa; Ahmed Elbeltagi; Zaher Mundher Yaseen; Shamsuddin Shahid; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2022)

Caralluma tuberculata exhibits analgesic and anti-arthritic potential by downregulating pro-inflammatory cytokines and attenuating oxidative stress - Syed Ihtisham Haider; Awais Asif; Hafiz Muhammad Farhan Rasheed; Adnan Akram; Qaiser Jabeen (Inflammopharmacology, 2022)

Silencing of Curlin Protein via M13 Phagemid-Mediated Synthetic sRNA Expression Reduces Virulence in the Avian Pathogenic E. coli (APEC) - Sayed Abdullah; Quratul Ain; Amna Jalil; Dilawar Khan; Arsalan Khan; Muhammad Qasim; Malik Badshah; Fazal Adnan (Current Microbiology, 2022)

Competency of groundwater recharge of irrigated cotton field subjacent to sowing methods, plastic mulch, water productivity, and yield under climate change - Muhammad Saeed; Ahsan Maqbool; Muhammad Adnan Ashraf; Muhammad Arshad; Kashif Mehmood; Muhammad Usman; Muhammad Arslan Farid (Environmental Science and Pollution Research, 2022)
Irrigated agriculture is a foremost consumer of water resources to fulfill the demand for food and fiber with an increasing population under climate changes; cotton is no exception. Depleting groundwater recharge and water productivity is critical for the sustainable cotton crop yield peculiarly in the semiarid region. This study investigated the water productivity and cotton yield under six different treatments: three sowing methods, i.e., flat, ridge, and bed planting with and without plastic mulch. Cotton bed planting without mulch showed maximum water productivity (0.24 kg.m −3 ) and the highest cotton yield (1946 kg.ha −1 ). Plastic mulching may reduce water productivity and cotton yield. HYDRUS-1D unsaturated flow model was used to access the groundwater recharge for 150 days under six treatments after model performance evaluation. Maximum cumulative recharge was observed 71 cm for the flat sowing method without plastic mulch. CanESM2 was used to predict climate scenarios for RCP 2.6, 4.5, and 8.5 for the 2050s and 2080s by statistical downscale modeling (SDSM) using historical data from 1975 to 2005 to access future groundwater recharge flux. Average cumulative recharge flux declined 36.53% in 2050 and 22.91% in 2080 compared to 2017 without plastic mulch. Multivariate regression analysis revealed that a maximum 23.78% reduction in groundwater recharge could influence future climate change. Further study may require to understand the remaining influencing factor of depleting groundwater recharge. Findings highlight the significance of climate change and the cotton sowing method while accessing future groundwater resources in irrigated agriculture.

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Value addition and risk assessment of dairy digestate as biofertilizer on crop yield and soil fertility - Sidra Mukhtar; Abdullah Yasar; Yusra Mahfooz; Rizwan Rasheed; Amtul Bari Tabinda; Muhammad Adnan Ashraf; Muhammad Nauman; Afifa Malik (Arabian Journal of Geosciences, 2022)

The potential of a novel support vector machine trained with modified mayfly optimization algorithm for streamflow prediction - Rana Muhammad Adnan; Ozgur Kisi; Reham R. Mostafa; Ali Najah Ahmed; Ahmed El-Shafie (Hydrological Sciences Journal, 2022)

Assessment of residents’ perceptions and support toward development projects: A study of the China–Pakistan Economic Corridor - Shamsa Kanwal; Abdul Hameed Pitafi; Muhammad Imran Rasheed; Adnan Pitafi; Jawad Iqbal (The Social Science Journal, 2022)

Separation and remediation of environmental pollutants using metal–organic framework-based tailored materials - Walter Dzumbira; Nisar Ali; Chuansong Duanmu; Yong Yang; Adnan Khan; Farman Ali; Muhammad Bilal; Lotfi Aleya; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Modeling of rainfall–runoff events using HEC-HMS model in southern catchments of Jerusalem Desert-Palestine - Mohammad Omar Ahmad Shakarneh; Asim Jahangir Khan; Qaisar Mahmood; Romana Khan; Muhammad Shahzad; Adnan Ahmad Tahir (Arabian Journal of Geosciences, 2022)

Quantifying climate-induced drought risk to livelihood and mitigation actions in Balochistan - Muhammad Ashraf; Adnan Arshad; Praharsh M. Patel; Adeel Khan; Huma Qamar; Ristina Siti-Sundari; Muhammad Usman Ghani; Ali Amin; Jamilur Rehman Babar (Natural Hazards, 2021)

Anti-neuropathic pain activity of a cationic palladium (II) dithiocarbamate by suppressing the inflammatory mediators in paclitaxel-induced neuropathic pain model - Muhammad Naveed; Rahim Ullah; Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Shahan Zeb Khan; Zia ur Rehman; Salman Khan (Molecular Biology Reports, 2021)

Soil microbial biomass and extracellular enzyme–mediated mineralization potentials of carbon and nitrogen under long-term fertilization (> 30 years) in a rice–rice cropping system - Muhammad Nadeem Ashraf; Gao Jusheng; Wu Lei; Adnan Mustafa; Ahmed Waqas; Tariq Aziz; Waqas-ud-Din Khan; Shafeeq-ur-Rehman; Babar Hussain; Muhammad Farooq; Zhang Wenju; Xu Minggang (Journal of Soils and Sediments, 2021)

Analysis of food resources, host availability and insecticidal impacts on the fecundity, longevity and parasitism efficiency of Diaertiella rapae (M’intosh) - Ahmad Nawaz; Habib Ali; Sajid Fiaz; Muhammad Sufyan; Miza Abdul Qayyum; Rashid Azad; Yasir Niaz; Muhamamd Adnan Bodlah; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Geological and Geomorphological Characteristics of Hingol National Park (HNP), Balochistan: a Geoheritage Candidate from Southern Pakistan - Muhammad Yaseen; Abbas Ali Naseem; Jawad Ahmad; Afrasiab Khan; Abdullah Khan; Muhammad Alamzeb; Adnan Ahmad; Usman Saeed; Arsalan Ahmad (Geoheritage, 2021)

Screening of wheat (Triticum aestivum L.) genotypes for drought tolerance using polyethylene glycol - Muhammad Adnan Bukhari; Adnan Noor Shah; Shah Fahad; Javaid Iqbal; Fahim Nawaz; Abdul Manan; Mohammad Safdar Baloch (Arabian Journal of Geosciences, 2021)

Assessment of Microscopic Detection of Malaria with Nested Polymerase Chain Reaction in War-Torn Federally Administered Tribal Areas of Pakistan - Muhammad Faisal Nadeem; Aamer Ali Khattak; Nadia Zeeshan; Usman Ayub Awan; Adnan Yaqoob (Acta Parasitologica, 2021)

Pollution characteristics and human health risk assessments of toxic metals and particle pollutants via soil and air using geoinformation in urbanized city of Pakistan - Khalid Mehmood; Yansong Bao; Roman Abbas; Saifullah; George P. Petropoulos; Hamaad Raza Ahmad; Muhammad Mohsin Abrar; Adnan Mustafa; Alwaseela Abdalla; Katia Lasaridi; Shah Fahad (Environmental Science and Pollution Research, 2021)

A bibliometric analysis and systematic literature review of tourism-environmental degradation nexus - Muhammad Shahbaz; Muhammad Farhan Bashir; Muhammad Adnan Bashir; Luqman Shahzad (Environmental Science and Pollution Research, 2021)

Experimental and comparative study of Chinese commercial improved coal-fired cooking and space-heating stoves - Riaz Ahmad; Adnan Abbas; Wang Jufei; Li Hua; Muhammad Sultan; Bohong Li; Samuel M Nyambura; Pan Xingjia (Environmental Science and Pollution Research, 2021)

Exposure of broiler chickens to chronic heat stress increases the severity of white striping on the pectoralis major muscle - Muhammad Adnan Aslam; Emrah İpek; Roshan Riaz; Şule Yurdagül Ӧzsoy; Waseem Shahzad; Ӧzay Güleş (Tropical Animal Health and Production, 2021)

Analysis of income inequality and environmental pollution in BRICS using fresh asymmetric approach - Weijun Zhao; Muhammad Hafeez; Adnan Maqbool; Sana Ullah; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Fluctuation Dynamics of Radon in Groundwater Prior to the Gansu Earthquake, China (22 July 2013: Ms = 6.6): Investigation with DFA and MFDFA Methods - Aftab Alam; Nanping Wang; Ermioni Petraki; Adnan Barkat; Fuqiong Huang; Muhammad Ali Shah; Demetrios Cantzos; Georgios Priniotakis; Panayiotis H. Yannakopoulos; Michail Papoutsidakis; Dimitrios Nikolopoulos (Pure and Applied Geophysics, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Prediction of changes in water balance of Nam Co Lake under projected climate change scenarios - Muhammad Adnan; Shichang Kang; Muhammad Saifullah; Shiyin Liu; Guoshuai Zhang; Qiudong Zhao; Muhammad Abrar Faiz; Muhammad Zaman (Hydrological Sciences Journal, 2021)

Correction to: The trade-off between economic growth and environmental quality: does economic freedom asymmetric matter for Pakistan? - Muhammad Tariq Majeed; Zhiyuan Yu; Adnan Maqbool; Mesfin G. Genie; Sana Ullah; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

The trade-off between economic growth and environmental quality: does economic freedom asymmetric matter for Pakistan? - Muhammad Tariq Majeed; Zhiyuan Yu; Adnan Maqbool; Mesfin Genie; Sana Ullah; Waheed Ahmad (Environmental Science and Pollution Research, 2021)

Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Long-term fertilization alters chemical composition and stability of aggregate-associated organic carbon in a Chinese red soil: evidence from aggregate fractionation, C mineralization, and 13C NMR analyses - Adnan Mustafa; Xu Hu; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Ali Akbar Maitlo; Kashif Ali Kubar; Qudsia Saeed; Muhammad Kamran; Muhammad Naveed; Wang Boren; Sun Nan; Xu Minggang (Journal of Soils and Sediments, 2021)

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Saba Shahrum; Shanila Zahra; Saima Shabbir; Azhar Iqbal (Journal of Fluorescence, 2021)

Evaluation of One Belt One Road publications: a bibliometric and literature review analysis - Muhammad Farhan Bashir; Benjiang MA; Yifang Qin; Muhammad Adnan Bashir (Environmental Science and Pollution Research, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Environmental quality, climate indicators, and COVID-19 pandemic: insights from top 10 most affected states of the USA - Bilal; Muhammad Farhan Bashir; Khurram Shahzad; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan; Tehreem Fatima; Umar Numan (Environmental Science and Pollution Research, 2021)

The nexus of sectoral-based CO2 emissions and fiscal policy instruments in the light of Belt and Road Initiative - Muhammad Waqas Akbar; Peng Yuelan; Adnan Maqbool; Zeenat Zia; Muhammad Saeed (Environmental Science and Pollution Research, 2021)

A feasibility study on microwave imaging of bone for osteoporosis monitoring - Bilal Amin; Atif Shahzad; Lorenzo Crocco; Mengchu Wang; Martin O’Halloran; Ana González-Suárez; Muhammad Adnan Elahi (Medical & Biological Engineering & Computing, 2021)

Scientific data-driven evaluation of academic publications on environmental Kuznets curve - Muhammad Farhan Bashir; Benjiang Ma; Muhammad Adnan Bashir; Bilal; Luqman Shahzad (Environmental Science and Pollution Research, 2021)

Analysis of environmental taxes publications: a bibliometric and systematic literature review - Muhammad Farhan Bashir; Benjiang MA; Bilal; Bushra Komal; Muhammad Adnan Bashir (Environmental Science and Pollution Research, 2021)

Short term rainfall-runoff modelling using several machine learning methods and a conceptual event-based model - Rana Muhammad Adnan; Andrea Petroselli; Salim Heddam; Celso Augusto Guimarães Santos; Ozgur Kisi (Stochastic Environmental Research and Risk Assessment, 2021)

Delineating Novel Therapeutic Drug and Vaccine Targets for Staphylococcus cornubiensis NW1T Through Computational Analysis - Mohibullah Shah; Samavia Jaan; Batool Fatima; Muhammad Sameem Javed; Adnan Amjad; Asifullah Khan; Sahib Gul Afridi; Umar Nishan; Anwar Iqbal; Haq Nawaz (International Journal of Peptide Research and Therapeutics, 2021)

Efficient water allocation strategy to overcoming water inequity crisis for sustainability of agricultural land: a case of Southern Punjab, Pakistan - Ahsan Maqbool; Muhammad Adnan Ashraf; Abdul Khaliq; Wang Hui; Muhammad Saeed (Stochastic Environmental Research and Risk Assessment, 2021)

Comparison of different methodologies for rainfall–runoff modeling: machine learning vs conceptual approach - Rana Muhammad Adnan; Andrea Petroselli; Salim Heddam; Celso Augusto Guimarães Santos; Ozgur Kisi (Natural Hazards, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Variability and Predictability of Summer Monsoon Rainfall over Pakistan - Muhammad Adnan; Firdos Khan; Nadia Rehman; Shaukat Ali; Sher Shah Hassan; Muhammad Mubashar Dogar; Shahbaz Mehmood; Shabehul Hasson (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Delineation of sinkhole in evaporite deposits using electrical resistivity survey: a case study of southern Kohat Plateau, Pakistan - Muhammad Waqar Azeem; Khaista Rehman; Nazeer Ur Rehman; Afrasiab; Umar Farooq; Adnan Arshad (Arabian Journal of Geosciences, 2021)

Growth regulation of Desmostachya bipinnata by organ-specific biomass, water relations, and ion allocation responses to improve salt resistance - Muhammad Yousuf Adnan; Tabassum Hussain; Muhammad Zaheer Ahmed; Bilquees Gul; M. Ajmal Khan; Brent L. Nielsen (Acta Physiologiae Plantarum, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

The comparative analysis of essential nutrient fractions in permafrost and different land use systems of Diamer Division, Gilgit-Baltistan - Didar Ahmad; Farhan Hafeez; Muhammad Irshad; Qaisar Mehmood; Adnan Ahmed Tahir; Akhtar Iqbal; Faridullah (Arabian Journal of Geosciences, 2020)

RETRACTED ARTICLE: Property market price response to flood-hazard - Muhammad Najib Razali; Siti Hafsah Zulkarnain; Zakri Tarmidi; Nurul Hana Adi Maimun; Yasmin Mohd. Adnan; Muhamad Ali Yuzir (Natural Hazards, 2020)

Biogeochemical transformation of greenhouse gas emissions from terrestrial to atmospheric environment and potential feedback to climate forcing - Awais Shakoor; Fatima Ashraf; Saba Shakoor; Adnan Mustafa; Abdul Rehman; Muhammad Mohsin Altaf (Environmental Science and Pollution Research, 2020)

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Dietary intake assessment of pyrethroid residues from okra and eggplant grown in peri-urban areas of Punjab, Pakistan - Adnan Amjad; Muhammad Atif Randhawa; Muhammad Sameem Javed; Zafarullah Muhammad; Mussawar Ashraf; Zulfiqar Ahmad; Shamas Murtaza (Environmental Science and Pollution Research, 2020)

Environmental pollution and COVID-19 outbreak: insights from Germany - Bilal; Muhammad Farhan Bashir; Maroua Benghoul; Umar Numan; Awais Shakoor; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan (Air Quality, Atmosphere & Health, 2020)

Foliar application of gibberellic acid endorsed phytoextraction of copper and alleviates oxidative stress in jute (Corchorus capsularis L.) plant grown in highly copper-contaminated soil of China - Muhammad Hamzah Saleem; Shah Fahad; Muhammad Adnan; Mohsin Ali; Muhammad Shoaib Rana; Muhammad Kamran; Qurban Ali; Inas A. Hashem; Parashuram Bhantana; Mubassir Ali; Reem M. Hussain (Environmental Science and Pollution Research, 2020)

Genetic mapping and identification of new major loci for tolerance to low phosphorus stress in rice - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Majeeduddin Solangi; Saba Khanzada; Muhammad Faheem; Jianmin Bian; Xiaohua Pan; Rui Cai Han; Xunfeng He; et al. (Physiology and Molecular Biology of Plants, 2020)
Phosphorus (P) is one of the essential macronutrients for rice. In this study, we used 120 rice backcross recombinant inbred lines (BRILs) derived from a cross indica cv. Changhui 891 and japonica cv. 02428. To elucidate the genetic control of P deficiency tolerance in rice, we have used high quality SNPs bin markers to identify some important loci underlying phosphorus deficiency. The bin map was generated which includes 3057 bins covering distance of 1266.5 cM with an average of 0.41 cM between markers. Based on this map, 50 loci, including four novel loci, qSL - 3 , qRL - 11 , qSDW - 1 , qRDW - 1 with phenotypic variance 23.26%, 12.06%, 9.89% associated with P deficiency-related seedling traits were identified. No significant QTLs was found for root length under P+, shoot fresh weight P− and root length, shoot fresh weight for P+, P− and their ratio respectively. Root fresh weight, and root dry weight were strongly correlated to each other, and QTLs for these variables were located on the same chromosome 1 at the same region. Notably, 3 pleiotropic regions is the pioneer of our study, and these regions would facilitate map-based cloning to expedite the MAS selection for developing low phosphorous tolerant varieties. This study not only improves our knowledge about molecular processes associated with P deficiency, but also provides useful information to understand the genetic architecture of low phosphorous tolerance.

Effective sequestration of Cr (VI) from wastewater using nanocomposite of ZnO with cotton stalks biochar: modeling, kinetics, and reusability - Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Hussnain Siddique; Zafar Iqbal; Muhammad Amjad; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Matrine alleviates neurobehavioral alterations via modulation of JNK-mediated caspase-3 and BDNF/VEGF signaling in a mouse model of burn injury - Adnan Khan; Bushra Shal; Muhammad Naveed; Bakht Nasir; Nadeem Irshad; Hussain Ali; Salman Khan (Psychopharmacology, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Transfer learning for neural network model in chlorophyll-a dynamics prediction by Wenchong Tian, Zhenliang Liao, and Xuan Wang - Rana Muhammad Adnan; Ozgur Kisi (Environmental Science and Pollution Research, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Erratum to: Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
The article Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018, written by Jawaria GUL, Sher MUHAMMAD, LIU Shi-yin, Siddique ULLAH, Shakeel AHMAD, Huma HAYAT and Adnan Ahmad TAHIR, was originally published Online First without Open Access. After publication in volume 17, issue 3, page 572-587, the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original version of this article has been revised due to a retrospective Open Access order.

Spatio-temporal assessment and climatology of atmospheric organic carbon over Pakistan - Muhammad Zaffar Hashmi; Khadija Ashraf; Shahzada Adnan; Shuhong Wang; Siwatt Pongpiachan; Xiaomei Su; Zulkfil Ahmed (Arabian Journal of Geosciences, 2020)

Modelling reference evapotranspiration by combining neuro-fuzzy and evolutionary strategies - Meysam Alizamir; Ozgur Kisi; Rana Muhammad Adnan; Alban Kuriqi (Acta Geophysica, 2020)

Formulation Development, Characterization, and Evaluation of a Novel Dexibuprofen-Capsaicin Skin Emulgel with Improved In Vivo Anti-inflammatory and Analgesic Effects - Imran Khan Burki; Muhammad Khalid Khan; Barkat Ali Khan; Bushra Uzair; Valdir A. Braga; Qazi Adnan Jamil (AAPS PharmSciTech, 2020)

Impact of jet stream and associated mechanisms on winter precipitation in Pakistan - Fayyaz Ahmed; Shahzada Adnan; Muhammad Latif (Meteorology and Atmospheric Physics, 2020)

Ameliorative Effects of Biochar on Rapeseed (Brassica napus L.) Growth and Heavy Metal Immobilization in Soil Irrigated with Untreated Wastewater - Muhammad Kamran; Zaffar Malik; Aasma Parveen; Li Huang; Muhammad Riaz; Saqib Bashir; Adnan Mustafa; Ghulam Hassan Abbasi; Bin Xue; Umeed Ali (Journal of Plant Growth Regulation, 2020)

Achieving environmental sustainability through information technology: “Digital Pakistan” initiative for green development - Hassan Ahmad Nizam; Khalid Zaman; Khan Burhan Khan; Rubeena Batool; Muhammad Adnan Khurshid; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2020)

Spatio-temporal changes in the six major glaciers of the Chitral River basin (Hindukush Region of Pakistan) between 2001 and 2018 - Jawaria Gul; Sher Muhammad; Shi-yin Liu; Siddique Ullah; Shakeel Ahmad; Huma Hayat; Adnan Ahmad Tahir (Journal of Mountain Science, 2020)
Glaciers in the northern Pakistan are a distinctive source of freshwater for the irrigation, drinking and industrial water supplies of the people living in those regions and downstream. These glaciers are under a direct global warming impact as indicated in many previous studies. In this study, we estimated the glacier dynamics in terms of Equilibrium Line Altitude (ELA), mass balance and the snout position variation using remote sensing data between 2001 and 2018. Six glaciers, having area ≥ 20 km 2 each, situated in the Chitral region (Hindukush Mountains) were investigated in this study. Digital Elevation Model (DEM) and available cloud-free continuous series of Landsat and Sentinel the entire study area was a retreat of -231 ± 140 m. No obvious relationship was found between the glacier variation trends and the available gauged climatic data possibly due to the presence of debris cover in ablation zones of all the studied glaciers which provides insulation and reduces the immediate climatic effects.

Spatio-Temporal Variability of Summer Monsoon Onset over Pakistan - Shaukat Ali; Bushra Khalid; Rida Sehar Kiani; Romaisa Babar; Sana Nasir; Nadia Rehman; Muhammad Adnan; Muhammad Arif Goheer (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Reservoir Inflow Prediction by Ensembling Wavelet and Bootstrap Techniques to Multiple Linear Regression Model - Adnan Bashir; Muhammad Ahmed Shehzad; Ijaz Hussain; Muhammad Ishaq Asif Rehmani; Sajjad Haider Bhatti (Water Resources Management, 2019)

Zinc and iron complexes of oleanolic acid, (OA) attenuate allergic airway inflammation in rats - Adnan Jehangir; Muhammad Shahzad; Khadija Shahid; Akbar Waheed; Farhana Ayub (Inflammopharmacology, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Thidiazuron-induced efficient biosynthesis of phenolic compounds in callus culture of Ipomoea turbinata Lagasca and Segura - Waqar Ahmad; Adnan Zahir; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2019)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Physiological response of spinach to toxic heavy metal stress - Muhammad Zubair; Qudrat Ullah Khan; Nosheen Mirza; Rizwana Sarwar; Asghar Ali Khan; Mohammad Safdar Baloch; Shah Fahad; Adnan Noor Shah (Environmental Science and Pollution Research, 2019)

Long-term ENSO relationship to precipitation and storm frequency over western Himalaya–Karakoram–Hindukush region during the winter season - Shahzad Kamil; Mansour Almazroui; In-Sik Kang; Muhammad Hanif; Fred Kucharski; Muhammad Adnan Abid; Fahad Saeed (Climate Dynamics, 2019)

Dynamic linkages between tourism, energy, environment, and economic growth: evidence from top 10 tourism-induced countries - Kanwal Shaheen; Khalid Zaman; Rubeena Batool; Muhammad Adnan Khurshid; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Economics of death and dying: a critical evaluation of environmental damages and healthcare reforms across the globe - Rubeena Batool; Khalid Zaman; Muhammad Adnan Khurshid; Salman Masood Sheikh; Alamzeb Aamir; Alaa Mohamd Shoukry; Mohamed A. Sharkawy; Fares Aldeek; Jameel Khader; Showkat Gani (Environmental Science and Pollution Research, 2019)

Pan evaporation modeling by three different neuro-fuzzy intelligent systems using climatic inputs - Rana Muhammad Adnan; Anurag Malik; Anil Kumar; Kulwinder Singh Parmar; Ozgur Kisi (Arabian Journal of Geosciences, 2019)

RETRACTED ARTICLE: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Thunderstorm frequency distribution and associated convective mechanisms over Pakistan - Rehan Ahmed; Muhammad Latif; Shahzada Adnan; Muhammad Khubaib Abuzar (Theoretical and Applied Climatology, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Evaluation of SWAT Model performance on glaciated and non-glaciated subbasins of Nam Co Lake, Southern Tibetan Plateau, China - Muhammad Adnan; Shi-change Kang; Guo-shuai Zhang; Muhammad Naveed Anjum; Muhammad Zaman; Yu-qing Zhang (Journal of Mountain Science, 2019)

Chemogenic silver nanoparticles enhance lignans and neolignans in cell suspension cultures of Linum usitatissimum L. - Adnan Zahir; Muhammad Nadeem; Waqar Ahmad; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

A new sulphated flavone and other phytoconstituents from the leaves of Tetracera indica Merr. and their alpha-glucosidase inhibitory activity - Alhassan Muhammad Alhassan; Qamar Uddin Ahmed; Jalifah Latip; Syed Adnan Ali Shah (Natural Product Research, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Dielectric properties of bones for the monitoring of osteoporosis - Bilal Amin; Muhammad Adnan Elahi; Atif Shahzad; Emily Porter; Barry McDermott; Martin O’Halloran (Medical & Biological Engineering & Computing, 2019)

Multi-precursory Analysis of Phalla Earthquake (July 2015; Mw 5.1) Near Islamabad, Pakistan - Adnan Barkat; Aamir Ali; Khaista Rehman; Muhammad Awais; Muhammad Arslan Tariq; Junaid Ahmed; Muhammad Ayaz Amin; Talat Iqbal (Pure and Applied Geophysics, 2018)

Stream Flow Forecasting of Poorly Gauged Mountainous Watershed by Least Square Support Vector Machine, Fuzzy Genetic Algorithm and M5 Model Tree Using Climatic Data from Nearby Station - Rana Muhammad Adnan; Xiaohui Yuan; Ozgur Kisi; Muhammad Adnan; Asif Mehmood (Water Resources Management, 2018)

Yeast-extract improved biosynthesis of lignans and neolignans in cell suspension cultures of Linum usitatissimum L. - Muhammad Nadeem; Bilal Haider Abbasi; Laurine Garros; Samantha Drouet; Adnan Zahir; Waqar Ahmad; Nathalie Giglioli-Guivarc’h; Christophe Hano (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Phytohormones enhanced drought tolerance in plants: a coping strategy - Abid Ullah; Hakim Manghwar; Muhammad Shaban; Aamir Hamid Khan; Adnan Akbar; Usman Ali; Ehsan Ali; Shah Fahad (Environmental Science and Pollution Research, 2018)

Sustainable survival under climatic extremes: linking flood risk mitigation and coping with flood damages in rural Pakistan - Azhar Abbas; T. S. Amjath-Babu; Harald Kächele; Muhammad Usman; M. Amjed Iqbal; Muhammad Arshad; M. Adnan Shahid; Klaus Müller (Environmental Science and Pollution Research, 2018)

Role of sorption energy and chemisorption in batch methylene blue and Cu2+ adsorption by novel thuja cone carbon in binary component system: linear and nonlinear modeling - Saeed Rehman; Adnan Adil; Ahsan Jabbar Shaikh; Jehanzeb Ali Shah; Muhammad Arshad; Muhammad Arif Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2018)

Interaction between PGPR and PGR for water conservation and plant growth attributes under drought condition - Naeem Khan; Asghari Bano; Muhammad Adnan Shahid; Wajid Nasim; MD Ali Babar (Biologia, 2018)

Projection of future streamflow of the Hunza River Basin, Karakoram Range (Pakistan) using HBV hydrological model - Ayaz Fateh Ali; Cun-de Xiao; Xiao-peng Zhang; Muhammad Adnan; Mudassar Iqbal; Garee Khan (Journal of Mountain Science, 2018)

Effect of gut bacteria on fitness of the Chinese citrus fly, Bactrocera minax (Diptera: Tephritidae) - Muhammad Adnan Rashid; Awawing Anjwengwo Andongma; Yong-Cheng Dong; Xue-Ming Ren; Chang-Ying Niu (Symbiosis, 2018)

Monthly runoff forecasting based on LSTM–ALO model - Xiaohui Yuan; Chen Chen; Xiaohui Lei; Yanbin Yuan; Rana Muhammad Adnan (Stochastic Environmental Research and Risk Assessment, 2018)

Genetic diversity and recombination analysis based on capsid protein gene of Chilli veinal mottle virus isolates from Pakistan - Adnan Ahmad; Muhammad Ashfaq (European Journal of Plant Pathology, 2018)

Ensembling Downscaling Techniques and Multiple GCMs to Improve Climate Change Predictions in Cryosphere Scarcely-Gauged Catchment - Muhammad Azmat; Muhammad Uzair Qamar; Shakil Ahmed; Muhammad Adnan Shahid; Ejaz Hussain; Sajjad Ahmad; Rao Arsalan Khushnood (Water Resources Management, 2018)

Liming induces carbon dioxide (CO2) emission in PSB inoculated alkaline soil supplemented with different phosphorus sources - Muhammad Adnan; Zahir Shah; Muhammad Sharif; Hidayatur Rahman (Environmental Science and Pollution Research, 2018)

Spatial modeling of rat bites and prediction of rat infestation in Peshawar valley using binomial kriging with logistic regression - Asad Ali; Farrah Zaidi; Syeda Hira Fatima; Muhammad Adnan; Saleem Ullah (Environmental Monitoring and Assessment, 2018)

Rat-bites of an epidemic proportion in Peshawar vale; a GIS based approach in risk assessment - Syeda Hira Fatima; Farrah Zaidi; Muhammad Adnan; Asad Ali; Qaiser Jamal; Muhammad Khisroon (Environmental Monitoring and Assessment, 2018)

Assessment of Air Temperature Trends in the Source Region of Yellow River and Its Sub-Basins, China - Mudassar Iqbal; Jun Wen; Xin Wang; Yongchao Lan; Hui Tian; Muhammad Naveed Anjum; Muhammad Adnan (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Influence of UV-A radiation on oxidative stress and antioxidant enzymes in Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2017)

Predicting Peak Flows in Real Time through Event Based Hydrologic Modeling for a Trans-Boundary River Catchment - Muhammad Adnan Shahid; Piero Boccardo; Muhammad Usman; Adriana Albanese; Muhammad Uzair Qamar (Water Resources Management, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Erratum to: Cost-effective enhanced iron bioavailability in rice grain grown on calcareous soil by sulfur mediation and its effect on heavy metals mineralization - Pia Muhammad Adnan Ramzani; Muhammad Khalid; Shazia Anjum; Waqas-ud-Din Khan; Shafaqat Ali; Fakhir Hannan; Muhammad Iqbal (Environmental Science and Pollution Research, 2017)

Cost-effective enhanced iron bioavailability in rice grain grown on calcareous soil by sulfur mediation and its effect on heavy metals mineralization - Pia Muhammad Adnan Ramzani; Muhammad Khalid; Shazia Anjum; Waqas-ud-Din Khan; Shafaqat Ali; Fakhir Hannan; Muhammad Iqbal (Environmental Science and Pollution Research, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

Chitosan alleviates phytotoxicity caused by boron through augmented polyamine metabolism and antioxidant activities and reduced boron concentration in Cucumis sativus L. - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Guodong David Liu; Lincoln Zotarelli; Naeem Khan (Acta Physiologiae Plantarum, 2017)

Haematology and blood chemistry references values for clinically healthy red-wattled lapwing (Vanellus indicus) - Sajid Umar; Kiran Aqil; Rizwan Qayyum; Muhammad Younus; Qamar-un-Nisa; Shahzad Ali; Muhammad Ali Shah; Muhammad Irfan; Muhammad Usman; Asif Ali; Akbar Ali; Adnan Ayan; et al. (European Journal of Wildlife Research, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Effect of different amendments on rice (Oryza sativa L.) growth, yield, nutrient uptake and grain quality in Ni-contaminated soil - Pia Muhammad Adnan Ramzani; Waqas-ud-Din Khan; Muhammad Iqbal; Salma Kausar; Shafaqat Ali; Muhammad Rizwan; Zaheer Abbas Virk (Environmental Science and Pollution Research, 2016)

Effect of UV-A radiation as an environmental stress on the development, longevity, and reproduction of the oriental armyworm, Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Molecular characterization and growth optimization of halo-tolerant protease producing Bacillus Subtilis Strain BLK-1.5 isolated from salt mines of Karak, Pakistan - Nawab Ali; Nimat Ullah; Muhammad Qasim; Hazir Rahman; Shahid Niaz Khan; Abdul Sadiq; Muhammad Adnan (Extremophiles, 2016)

Parameter Identification of Nonlinear Muskingum Model with Backtracking Search Algorithm - Xiaohui Yuan; Xiaotao Wu; Hao Tian; Yanbin Yuan; Rana Muhammad Adnan (Water Resources Management, 2016)

Foliar treatment with Lolium perenne (Poaceae) leaf extract alleviates salinity and nickel-induced growth inhibition in pea - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Muhammad Akbar Anjum; Hafiz Haider Ali; Neil Scott Mattson; Francisco Garcia-Sanchez (Brazilian Journal of Botany, 2016)

The role of selenium in amelioration of heat-induced oxidative damage in cucumber under high temperature stress - Rashad Mukhatar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Muhammad Akbar Anjum; Francisco Garcia-Sanchez; Neil Scott Mattson (Acta Physiologiae Plantarum, 2016)

A critical re-evaluation of controls on spatial and seasonal variations in nitrate concentrations in river waters throughout the River Derwent catchment in North Yorkshire, UK - Shaheen Begum; Muhammad Adnan; Colin J. McClean; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2016)

Rice (Oryza sativa L.) hydraulic conductivity links to leaf venation architecture under well-watered condition rather than PEG-induced water deficit - Muhammad Adnan Tabassum; Yuhui Ye; Tingting Yu; Guanglong Zhu; Muhammad Shahid Rizwan; Muhammad Atif Wahid; Shaobing Peng; Yong Li (Acta Physiologiae Plantarum, 2016)

Accumulation of Residual Antibiotics in the Vegetables Irrigated by Pharmaceutical Wastewater - Shoaib Hussain; Muhammad Naeem; Muhammad Nawaz Chaudhry; Muhammad Adnan Iqbal (Exposure and Health, 2016)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Synthesis and structural elucidation of two new series of aurone derivatives as potent inhibitors against the proliferation of human cancer cells - Aboubaker A. Elhadi; Hasnah Osman; Muhammad Adnan Iqbal; Sharmila K. Rajeswari; Mohamed B. Khadeer Ahamed; Amin M.S. Abdul Majid; Mohd Mustaqim Rosli; Ibrahim Abdul Razak; Aman Shah Abdul Majid (Medicinal Chemistry Research, 2015)

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

Crossability among modern roses and heterosis of quantitative and qualitative traits in hybrids - Muhammad Nadeem; Adnan Younis; Atif Riaz; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2015)

Impact of rapid urbanization on microclimate of urban areas of Pakistan - Adnan Ahmad Tahir; Adnan Muhammad; Qaisar Mahmood; Sheikh Saeed Ahmad; Zahid Ullah (Air Quality, Atmosphere & Health, 2015)

Potential role of phytohormones and plant growth-promoting rhizobacteria in abiotic stresses: consequences for changing environment - Shah Fahad; Saddam Hussain; Asghari Bano; Shah Saud; Shah Hassan; Darakh Shan; Faheem Ahmed Khan; Fahad Khan; Yutiao Chen; Chao Wu; Muhammad Adnan Tabassum; Ma Xiao Chun; et al. (Environmental Science and Pollution Research, 2015)

Silicon-induced alleviation of NaCl toxicity in okra (Abelmoschus esculentus) is associated with enhanced photosynthesis, osmoprotectants and antioxidant metabolism - Tahira Abbas; Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Aslam Pervez; Chaudhary Muhammad Ayyub; Muhammad Anjum Aqueel; Muhammad Mansoor Javaid (Acta Physiologiae Plantarum, 2015)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

Fungal endophyte Penicillium janthinellum LK5 improves growth of ABA-deficient tomato under salinity - Abdul Latif Khan; Muhammad Waqas; Abdur Rahim Khan; Javid Hussain; Sang-Mo Kang; Syed Abdullah Gilani; Muhammad Hamayun; Jae-Ho Shin; Muhammad Kamran; Ahmed Al-Harrasi; Byung-Wook Yun; Muhammad Adnan; et al. (World Journal of Microbiology and Biotechnology, 2013)

Synthesis of metal(II) [M = Cu, Mn, Zn] Schiff base complexes and their Pro-apoptotic activity in liver tumor cells via caspase activation - Abeer Mohamed Farag; Teoh Siang Guan; Hasnah Osman; A. M. S. Abdul Majid; Muhammad Adnan Iqbal; Mohamed B. Khadeer Ahamed (Medicinal Chemistry Research, 2013)

Synthesis, structure, anticancer, and antioxidant activity of para-xylyl linked bis-benzimidazolium salts and respective dinuclear Ag(I) N-heterocyclic carbene complexes (Part-II) - Rosenani A. Haque; Muhammad Adnan Iqbal; Patrick Asekunowo; A. M. S. Abdul Majid; Mohamed B. Khadeer Ahamed; Muhammad Ihtisham Umar; Sawsan S. Al-Rawi; Fouad Saleih R. Al-Suede (Medicinal Chemistry Research, 2013)

Synthesis and anticancer activity of para-xylyl linked bis-benzimidazolium salts and respective Ag(I) N-heterocyclic carbene complexes - Muhammad Adnan Iqbal; Rosenani A. Haque; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid; Sawsan S. Al-Rawi (Medicinal Chemistry Research, 2013)

Molecular simulations of bergenin as a new urease inhibitor - Mohammad Arfan; Hazrat Amin; Inamullah Khan; Muhammad Raza Shah; Hamidullah Shah; Amir Zada Khan; Syed Muhammad Ashhad Halimi; Nematullah Khan; Waqar Ahmad Kaleem; Mughal Qayum; Adnan Shahidullah; Muhammad Azam Khan (Medicinal Chemistry Research, 2012)

The Use of Stem Cells’ Hematopoietic Stimulating Factors Therapy Following Spinal Cord Injury - Afshin A. Divani; Muhammad S. Hussain; Ella Magal; Robert F. Heary; Adnan I. Qureshi (Annals of Biomedical Engineering, 2007)